Near infrared absorbing glass and near infrared cutoff filter
By optimizing the composition of the near-infrared absorbing glass, including adjusting the CuO content and O/P ratio, the problem of difficult to take into account both the transmittance and barrier ability of the near-infrared cut-off filter in the prior art after thinning is solved, and efficient near-infrared barrier and good weather resistance are achieved.
Patent Information
- Application Number
- CN202180049196.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-10
- Filing Date
- 2021-05-31
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-05-31
AI Technical Summary
It is difficult for existing near-infrared cut-off filters to maintain high visible area transmittance and excellent near-infrared barrier capabilities after thinning, and also difficult to maintain weather resistance in high temperature and high humidity environments.
Near infrared absorbing glass containing more than 4 major cations is used, including P ions, Li ions, Cu ions, etc., and by adjusting the glass composition of the oxide reference, the CuO content and O/P ratio are optimized to improve the transmittance and absorption performance of the glass.
It is achieved that even under thinning, high visible area transmittance and excellent near-infrared barrier capability can be maintained, and the reduction of weather resistance can be suppressed in a high temperature and high humidity environment.
Smart Images

Figure CN115803295B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to near infrared absorbing glass and a near infrared cutoff filter. Background Art
[0002] In small cameras such as smartphones in recent years, the image information is not only digitized, but also various electronic calculations are performed on the image information to reconstruct the image. For example, extracting a specific object and adjusting the color and contrast of the image have become the mainstream. At this time, if color information that does not exist is input to the imaging element due to the reflection of light in the optical element, the information must be removed, which is not preferred.
[0003] The near infrared cut filter has a function of filtering out unnecessary near infrared light (wavelength 700 to 1200 nm) within the sensitivity wavelength range of the imaging element. Generally, the near infrared cut filter is often provided right in front of the imaging element.
[0004] As near-infrared cut filters, those made of near-infrared absorbing glass as a base material and polished on a flat plate are widely used.
[0005] Near infrared absorbing glass generally contains Cu ions. An example of the spectral transmission characteristics of near infrared absorbing glass is shown in Figure 1 It should be noted that Figure 1 The light absorption characteristics near the wavelength of 700 to 1200 nm are determined by the Cu ions (Cu 2+ Among them, glass containing Cu ions and P ions can show Cu ions (Cu 2+ ) has near-infrared absorption properties and is therefore useful as glass for near-infrared cutoff filters (see, for example, Patent Document 1).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-12630
[0009] exist Figure 1 In the transmittance curve after the wavelength of 600nm, the wavelength at which the transmittance reaches 50% is called the "half-value", which has become one of the main standards for near-infrared cut-off filters. The half-value varies depending on the specifications of the filter, but is mostly set in the wavelength range of 600nm to 650nm. As a general method to achieve the desired half-value, there are methods such as adjusting the thickness of the glass substrate according to the Lambert-Beer law, or adjusting the Cu ion (Cu) content in the glass. 2+) concentration in any condition. Summary of the invention
[0010] Problems to be solved by the invention
[0011] The near infrared cut filter is required to have not only excellent ability to cut near infrared rays (ie, to have a desired half value and low near infrared transmittance) but also high transmittance in the visible region (violet to red region).
[0012] In addition, in recent years, the imaging device modules installed in smartphones and the like have been required to be both compact and high-performance, and the thickness of the near-infrared cut filter has been required to be thinner. Therefore, in recent years, the thickness of the near-infrared absorbing glass has been expected to be reduced from the existing 1 mm to about 0.45 mm, 0.3 mm or 0.2 mm, and further to 0.1 mm.
[0013] If only the near-infrared absorbing glass is thinned, the optical density (number of moles × thickness) of CuO required for near-infrared absorption is reduced, resulting in a decrease in the near-infrared absorption efficiency. In order to solve this problem, it is considered to increase the amount of CuO. However, if only the amount of CuO is increased, the absorption of CuO reaches the visible region (i.e., the red region) near the wavelength of 600nm, and the transmittance on the short wavelength side also tends to decrease. Therefore, it is difficult to simultaneously maintain the transmittance in the visible region (purple region to red region) and the absorption of near-infrared rays.
[0014] In addition, for near-infrared absorbing glass, in order to provide a near-infrared cut filter suitable for use in a high-temperature and high-humidity environment, it is desired to suppress the reduction of weather resistance in a high-temperature and high-humidity environment. However, according to the research of the present inventors, it is not easy to suppress the reduction of weather resistance while maintaining the transmittance in the visible region (purple region to red region) and the absorption of near-infrared rays.
[0015] In view of the above situation, one embodiment of the present invention aims to provide a near-infrared absorbing glass which has high transmittance in the visible region (purple region to red region) even after thinning, has excellent near-infrared blocking ability, and can suppress the reduction of weather resistance, and a near-infrared cutoff filter made of the near-infrared absorbing glass.
[0016] Solutions to the problem
[0017] One embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 1”), comprising four or more main cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions,
[0018] Contains P ions, Li ions and Cu ions as essential cations,
[0019] and contains at least O ions as anions,
[0020] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0021] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0022] In the oxide-based glass composition,
[0023] On a molar basis,
[0024] The total content of the oxides of the above main cations is 90.0% or more,
[0025] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0026] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0027] The total content of B2O3 and SiO2 (B2O3+SiO2) is less than 3.0%,
[0028] CuO content is α1% or more,
[0029] α1 is a value calculated by the following formula 1,
[0030] (Formula 1)
[0031] α1=70400×exp(-2.855×R)
[0032] In the above formula 1,
[0033] R is the above-mentioned ratio (O ion / P ion).
[0034] In addition, one embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 2”), comprising four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions,
[0035] Contains P ions, Li ions and Cu ions as essential cations,
[0036] and contains at least O ions as anions,
[0037] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0038] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0039] In the oxide-based glass composition,
[0040] On a molar basis,
[0041] The total content of the oxides of the above main cations is 90.0% or more,
[0042] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0043] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0044] The total content of B2O3 and SiO2 (B2O3+SiO2) is less than 3.0%,
[0045] The above-mentioned near infrared absorbing glass satisfies the following formula 2:
[0046] (Formula 2)
[0047] C-3200×exp(-2.278×R)≥0
[0048] In the above formula 2,
[0049] C is the average CuO content per molar volume of glass (unit: mmol / cc),
[0050] R is the above-mentioned ratio (O ion / P ion).
[0051] In addition, one embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 3”), comprising four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions,
[0052] Contains P ions, Li ions and Cu ions as essential cations,
[0053] and contains at least O ions as anions,
[0054] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0055] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0056] In the oxide-based glass composition,
[0057] On a molar basis,
[0058] The total content of the oxides of the above main cations is 90.0% or more,
[0059] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0060] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0061] A1 calculated by the following formula 3 is 2500 or more,
[0062] (Formula 3)
[0063] A1={O(P)-O(others)}×Cu
[0064] In the above formula 3,
[0065] O(P) represents the amount of oxygen in the oxide that constitutes P ions in the oxide-based glass composition.
[0066] O(others) represents the amount of oxygen obtained by removing the above O(P) from the amount of oxygen in the oxide constituting the above main cation in the glass composition based on oxides.
[0067] Cu represents the CuO content on a molar basis in the glass composition on an oxide basis.
[0068] In addition, one embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 4”), comprising four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions,
[0069] Contains P ions, Li ions and Cu ions as essential cations,
[0070] and contains at least O ions as anions,
[0071] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0072] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0073] In the oxide-based glass composition,
[0074] On a molar basis,
[0075] The total content of the oxides of the above main cations is 90.0% or more,
[0076] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0077] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0078] A2 calculated by the following formula 4 is 700 or more,
[0079] (Formula 4)
[0080] A2={O(P)-O(others)}×C
[0081] In the above formula 4,
[0082] C is the average CuO content per molar volume of glass (unit: mmol / cc),
[0083] O(P) represents the amount of oxygen in the oxide that constitutes P ions in the oxide-based glass composition.
[0084] O(others) represents the amount of oxygen obtained by removing the above-mentioned O(P) from the amount of oxygen in the oxide constituting the above-mentioned main cation in the glass composition based on oxides.
[0085] One embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 5”), comprising four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions,
[0086] Contains P ions, Li ions and Cu ions as essential cations,
[0087] and contains at least O ions as anions,
[0088] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0089] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0090] In the oxide-based glass composition,
[0091] On a molar basis,
[0092] The total content of the oxides of the above main cations is 90.0% or more,
[0093] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0094] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0095] CuO content is α2% or more,
[0096] α2 is a value calculated by the following formula 5,
[0097] (Formula 5)
[0098] α2=(76522)×exp(-2.855×R)
[0099] In the above formula 5,
[0100] R is the above-mentioned ratio (O ion / P ion).
[0101] In addition, one embodiment of the present invention relates to a near-infrared absorbing glass (hereinafter also referred to as “glass 6”), comprising four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions,
[0102] Contains P ions, Li ions and Cu ions as essential cations,
[0103] and contains at least O ions as anions,
[0104] The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.15 or less,
[0105] In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more.
[0106] In the oxide-based glass composition,
[0107] On a molar basis,
[0108] The total content of the oxides of the above main cations is 90.0% or more,
[0109] The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%,
[0110] The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less,
[0111] The above-mentioned near infrared absorbing glass satisfies the following formula 6,
[0112] (Formula 6)
[0113] C-(3478)×exp(-2.278×R)≥0
[0114] In the above formula 6,
[0115] C is the average CuO content per molar volume of glass (unit: mmol / cc),
[0116] R is the above-mentioned ratio (O ion / P ion).
[0117] Effects of the Invention
[0118] According to one embodiment of the present invention, it is possible to provide a near-infrared absorbing glass which has a high transmittance in the visible region (purple region to red region) even after thinning, has excellent near-infrared shielding capability, and can suppress the reduction of weather resistance. Furthermore, according to one embodiment of the present invention, it is possible to provide a near-infrared cut filter made of such near-infrared absorbing glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0119] Figure 1 An example of the spectral transmission characteristics of the near-infrared absorbing glass is shown. DETAILED DESCRIPTION
[0120] [Near infrared absorbing glass]
[0121] Hereinafter, Glasses 1 to 6 are also collectively referred to as “glass” or “near infrared absorbing glass”. Unless otherwise specified, descriptions related to glass composition and physical properties are applicable to all glasses in Glasses 1 to 6.
[0122] In the present invention and this specification, near-infrared absorbing glass refers to glass having the property of absorbing at least the entire region or part of the wavelength of the near-infrared wavelength range (wavelength 700 to 1200 nm). In addition, the near-infrared absorbing glass of one embodiment of the present invention contains O ions as constituent ions, and therefore, it can be oxide glass. Oxide glass refers to glass whose main network-forming component of glass is oxide. In addition, the near-infrared absorbing glass of one embodiment of the present invention contains O ions (anions) and P ions (cations) as constituent ions, and therefore, it can be phosphate glass. It should be noted that O ions are anions of oxygen atoms, and are also commonly referred to as oxide ions.
[0123] Hereinafter, glasses 1 to 6 will be described in more detail.
[0124] <Glass composition>
[0125] (Analysis Method)
[0126] The various components constituting glass can be quantified by known methods such as inductively coupled plasma atomic emission spectrometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS).
[0127] Anion components contained in glass can be identified and quantified by a known analytical method, for example, ion chromatography, non-dispersive infrared absorption (ND-IR) or the like.
[0128] In the present invention and this specification, "the content of a component is 0%, is not contained, or is not introduced" means that the component is not substantially contained, but inclusion of the component at an unavoidable impurity level is permitted.
[0129] (Description of glass composition based on oxides)
[0130] Based on the results obtained by the above analysis, the content (unit: mol %) of each component in the oxide-based glass composition can be calculated. The specific method is as follows.
[0131] The content of element i (mass % of element P) obtained by the above-mentioned analysis method i ) divided by the atomic weight M of element i i , from which we can find the number of moles of each element n i =P i / M i .
[0132] In the above-mentioned element i is a cationic component A i In the case ofi Replace with the corresponding number of moles of oxide n' i Specifically, the cationic component A corresponding to element i i The composition formula of the oxide is A i When xOy is expressed, n' i =n i / x.
[0133] In the above-mentioned element i, the anion component B other than O ion i In the case of i Later recorded as m i .
[0134] Cationic component A in the glass composition based on oxides i Oxide A i xOy content PA i (mol%) by PA i =n' i / (Σn' i +Σm i )×100.
[0135] The content in the glass composition based on oxides may also be referred to as an oxide-based fraction.
[0136] In the oxide-based glass composition, the anion components B other than O ions i Oxide base fraction PB i (mol%) from PB i =m i / (Σn' i +Σm i )×100.
[0137] Here, Σn' i It is the oxide of the cationic component contained in the glass. i The total number of moles of xOy. The effective figures of the content are used so that even if trace amounts of components are ignored, the calculation results will not be affected.
[0138] (Anion %)
[0139] “Anion %” refers to the value calculated by “(content of anion i of interest expressed in mol %) / (total number of anions contained in glass expressed in mol %)×100”, and refers to the molar percentage of the anion amount of interest relative to the total amount of anions.
[0140] The anion percentage of O ions in the above description of the oxide-based glass composition can be expressed as (ΣO i -Σ(Nk / 2)B k ) / (ΣO i -Σ(N k / 2)B k +ΣB k )×100, where A i xOy represents the cationic component A corresponding to element i i The composition formula of the oxide is as follows, and the cationic component A is used i Oxide base fraction PA i (mol%) of cationic component A i The number of O contained in the oxide is expressed as O i =PA i ×y, the anion component B k The valence number is expressed as N k .
[0141] Here, ΣO i is the sum of the molar numbers of O ions in the glass composition based on oxides, Σ(N k / 2)B k Indicates that the anion component B k The number of moles of O ions replaced. i -Σ(N k / 2)B k ) is the molar number of O ions contained in the glass.
[0142] On the other hand, in the present invention and this specification, regarding the oxygen content, when no anion components other than oxygen are detected by analysis based on a known method, all of the anion components (ie, 100 anion %) are O ions.
[0143] (Cationic component)
[0144] Regarding the valence of the cationic component, the formal valence of each cation is used. The formal valence refers to the valence necessary for the oxide of the cation of interest to maintain electrical neutrality when the valence of the O ions constituting the oxide is set to -2, and can be clearly determined from the chemical formula of the oxide.
[0145] For example, regarding Cu ions, in order to maintain the O contained in the chemical formula of the oxide CuO 2- The electronegativity of Cu is +2. In addition, for example, P ions are required to maintain the O contained in the chemical formula of the oxide P2O5. 2-The valence of P is +2×5 / 2=+5 due to its electrical neutrality with P. If this is summarized, the formal valence of the cation Ai contained in the oxide AixOy is "+2y / x". Therefore, when analyzing the glass composition, the valence of the cation does not need to be analyzed.
[0146] In addition, regarding the valence of anions (for example, the valence of O ions is -2), it is also a formal valence based on the idea that O ions accept two electrons and take a closed shell structure. Therefore, when analyzing the glass composition, it is not necessary to analyze the valence of anions. 2+ Part of it may become Cu during melting + , but usually its amount is very small, so the valence of Cu can all be regarded as +2.
[0147] (Anionic component)
[0148] The above-mentioned glass contains at least O ions as anions, and its content is 90.0 anion% or more in the glass composition expressed as anion%. The inventors believe that by reducing the O / P ratio in the glass mainly composed of O ions as anions, the absorption of CuO in the red region can be shifted to the long wavelength side, thereby increasing the content of CuO and improving the near-infrared blocking ability without reducing the transmittance in the red region. The O ion content in the glass composition expressed as anion% is 90.0% or more, preferably 95.0% or more, more preferably 98.0% or more, and further preferably 99.0% or more. From the perspective of suppressing volatilization during glass melting, it is also preferred that the proportion of O ions in the anion components is high. From the perspective of suppressing the generation of ribs, it is preferred to suppress volatilization during glass melting. In particular, from the perspective of suppressing volatilization during glass melting, improving productivity, and suppressing the generation of harmful gases during manufacturing, the content of O ions is preferably 100%. It should be noted that the formal valence of O ions is -2.
[0149] The glass may contain only O ions as anions in one embodiment, and may contain O ions and one or more other anions in another embodiment. Other anions include F ions, Cl ions, Br ions, I ions, etc. It should be noted that the formal valence of F ions, Cl ions, Br ions, and I ions is -1.
[0150] From the viewpoint of improving the homogeneity and strength of the glass, in the glass composition expressed as anion %, the content of F ions is preferably 15.0 anion % or less, more preferably 10.0 anion % or less, further preferably 5.0 anion % or less, further preferably 2.0 anion % or less, and further preferably 1.0 anion % or less. In particular, from the viewpoint of suppressing volatilization during glass melting, improving productivity, and suppressing the generation of harmful gases during manufacturing, the above-mentioned glass may be a glass that does not contain F ions.
[0151] (O / P ratio)
[0152] The molar ratio of the content of cations to the content of anions is the ratio of the contents (expressed in mole %) of the components of interest when the total amount of all cationic components and all anionic components is set to 100 mole %. Therefore, the ratio of the content of O ions to the content of P ions (O ions / P ions) is the ratio of the content of O ions (expressed in mole %) to the content of P ions (expressed in mole %) when the total amount of all cationic components and all anionic components is set to 100 mole %.
[0153] O / P ratio calculation method1
[0154] The O / P ratio (also described as R) can be calculated as follows based on the description of the above-described oxide-based glass composition:
[0155] A i xOy represents the cationic component A corresponding to element i i The composition formula of the oxide of the cationic component Ai is obtained by using the oxide reference fraction PAi (mol %) of the cationic component Ai and setting the number of O contained in the oxide of the cationic component Ai to O i =PA i ×y, the anion component B k The valence number is set to N k hour,
[0156] Formula D1: R1 = ΣO i -Σ(N k / 2)B k
[0157] Formula D2: R2 = P ion oxide (i.e. P2O5) base fraction (mol%) × 2
[0158] The O / P ratio (R) is calculated by the formula D3: R=R1 / R2.
[0159] For example, the following comparative example A is used as an example. The contents of the oxide-based glass composition of comparative example A are as follows: P2O5=53.59, Li2O=19.30, and CuO=27.11 in terms of mole %. The number of O contained in the molecular formula is: 5 for P2O5, 1 for Li2O, and 1 for CuO. The number of moles of O contained in the molecular formula is: 267.95 for P2O5, 19.30 for Li2O, and 27.11 for CuO.
[0160] The O / P ratio of the glass of this example can be calculated as follows.
[0161] Find the molecular formula of the glass: 53.59P2O5-19.30Li2O-27.11The number of O ions in CuO S The molecular formula of glass refers to a composition formula of glass expressed so that the total of molecules contained in the glass is 100.
[0162] That is, the number of O ions contained in the molecular formula MxOy of each oxide (P2O5: 5, Li2O: 1, CuO: 1) is used to calculate the N S =53.59×5+19.30×1+27.11×2=314.36 Calculate N S .
[0163] For the glass of the above example, in the molecular formula of the glass, the number of O ions replaced by other anions is zero. S =314.36 divided by the molar number of P contained in P2O5 53.59×2 to obtain the O / P ratio = 314.36 / (53.59×2) = 2.93…
[0164] O / P ratio calculation method 2
[0165] When one or more anion components other than oxygen are detected by analysis based on a known method, the oxygen content can be the following content (unit: anion %): the content calculated by the following method (3) from (1) the content of cations based on the valence of the cationic components contained in the glass and the molar % of the elements, and (2) the content of anions based on the valence of the anionic components other than oxygen and the molar % of the elements.
[0166] That is, according to the results of identification and quantitative analysis based on known methods,
[0167] (1) Regarding the cation components contained in the glass, the total cation content U is calculated based on the number of oxygen y and the number of cations x in the oxide MxOy, the number of oxygens per cation y / x×the mole % of the element.
[0168] (2) Regarding anion components other than oxygen, the total V of "the content of anions based on the molar % of the element × the average number of oxygen substituted per anion z / 2" is calculated based on the results of identification and quantitative analysis based on known methods and the valence z of the anions.
[0169] (3) UV may also be used as the content ratio of O ions to P ions.
[0170] As calculation examples of calculation method 2, the following calculation examples 1 and 2 are shown.
[0171] Calculation Example 1: When the molar percentages of the elements of P ions, Li ions, and Cu ions are quantitatively determined to be 22.0, 8.0, and 5.5 (the content of the elements expressed in mole %), the y / x of the corresponding oxides: P2O5, Li2O, and CuO are 2.5, 0.5, and 1.0, respectively. Therefore, U=22×2.5+8×0.5+5.5×1.0=64.5, and V=0.
[0172] Therefore, the molar percentage of O ions based on the molar percentage of the element is 64.5 (the content of the element expressed in mol %).
[0173] Based on the ratio of the thus determined O ion value and the analyzed P ion molar percentage, it can be determined that O / P ratio = 64.5 / 22 = 2.93…
[0174] Calculation Example 2: When the molar percentages of P ions, Li ions, and Cu ions are quantitatively determined to be 22.0, 8.0, and 5.5 (the content of the elements expressed in mole %), and the molar percentage of F ions is quantitatively determined to be 4.0 (the content of the elements expressed in mole %), the corresponding oxides: P2O5, Li2O, and CuO have y / x of 2.5, 0.5, and 1.0, respectively, and the valence of F is -1. Therefore, U=22×2.5+8×0.5+5.5×1.0=64.5, and V=4×1 / 2=2.
[0175] Therefore, the molar percentage of O ions based on the molar percentage of the element is 62.5 (the content of the element expressed in mol %).
[0176] Based on the ratio of the value of O ions thus determined and the molar percentage of P ions analyzed, it can be determined that O / P ratio = 62.5 / 22 = 2.84…
[0177] In Glasses 1 to 6, the ratio of the O ion content to the P ion content (O / P ratio) is 3.15 or less from the viewpoint of achieving both improved transmittance in the visible region and improved near-infrared shielding capability and improved thermal stability of the glass.
[0178] In glasses 1 to 6, the O / P ratio is preferably 3.14 or less, and more preferably 3.13 or less, 3.12 or less, 3.11 or less, 3.10 or less, 3.09 or less, 3.08 or less, 3.07 or less, 3.06 or less, 3.05 or less, 3.04 or less, 3.03 or less, 3.02 or less, 3.01 or less, and 3.00 or less.
[0179] On the other hand, from the viewpoint of improving weather resistance and / or suppressing a decrease in solubility, a larger O / P ratio is preferred in Glass 1 to Glass 6. From this viewpoint, in Glass 1 to Glass 6, the O / P ratio is preferably 2.50 or more, and more preferably in the order of 2.60 or more, 2.65 or more, 2.70 or more, 2.73 or more, 2.75 or more, 2.77 or more, 2.80 or more, 2.81 or more, 2.82 or more, 2.83 or more, 2.84 or more, 2.85 or more, 2.86 or more, 2.87 or more, 2.88 or more, 2.89 or more, and 2.90 or more.
[0180] (Cationic component)
[0181] Glasses 1 to 6 contain four or more main cations selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions, and contain P ions, Li ions, and Cu ions as essential cations. In the oxide-based glass compositions (molar basis) of Glasses 1 to 6, the total content of the oxides of the above main cations is 90.0% or more.
[0182] In glasses 1 to 6, the total content of the oxides of the main cations is 90.0% or more, which can help improve the thermal stability of the glass, and / or can help improve the optical homogeneity of the glass by suppressing striae, volatilization, etc. From the above aspects, the total content of the oxides of the main cations in glasses 1 to 6 is preferably 92.0% or more, and more preferably in the order of 93.0% or more, 95.1% or more, 96.1% or more, 97.1% or more, 98.1% or more, 98.6% or more, 99.1% or more, and 99.6% or more, and can also be 100%. In one embodiment, the total content of the oxides of the main cations in glasses 1 to 6 can also be 100% or less, or 99.5% or less, 99% or less, 98.5% or less, 98.0% or less, or 97.5% or less.
[0183] Hereinafter, the content of the cationic component will be described based on the content in the glass composition (molar basis) on an oxide basis.
[0184] CuO is an essential component for imparting near-infrared shielding capability to glass, and therefore, Glasses 1 to 6 contain Cu ions as essential cations.
[0185] In glass 1, the CuO content is α1% or more. α1 is a value calculated by the following formula 1.
[0186] (Formula 1)
[0187] α1=70400×exp(-2.855×R)
[0188] In Formula 1, R is the O / P ratio.
[0189] In addition, regarding Glass 2, the lower limit of the CuO content is defined by the following formula 2 from the CuO content per molar volume of glass.
[0190] (Formula 2)
[0191] C-3200×exp(-2.278×R)≥0
[0192] In Formula 2, C is the CuO content per molar volume of glass (unit: mmol / cc), and R is the O / P ratio.
[0193] In Formula 2, the above C is obtained by the following method.
[0194] The specific gravity of the glass is measured D (g / cc), and based on the glass composition obtained by analysis as described above, the mass equivalent to 1 mole of the glass composition, that is, the molar molecular weight M (g / mole), is calculated, and the molar volume of the glass M / D (unit: cc / mole) is calculated, and then C is calculated as C = molar % of CuO / (M / D) × 1000 (unit: mmol / cc).
[0195] The above-mentioned molar molecular weight M can be calculated as follows:
[0196] Based on the description of the above-mentioned oxide-based glass composition, the formula weight of the oxide corresponding to the above-mentioned cation component Ai is set to MA i , the anion component B k The atomic weight is MB k , and the atomic weight of oxygen is set to Mo, and M={Σ(PA i ×MA i )+Σ(PB k ×MB k )-Σ(N k / 2)Mo} / ΣPA i Calculate the above molar molecular weight M.
[0197] For example, the glass composition is composed of an A2O component of s mol% based on oxides, a BO component of t mol% based on oxides, and a F component of u mol%, s+t+u=100(%), and the formula weight of the A2O component is M A (g / mole), the formula weight of BO component is M B (g / mole), the atomic weight of F is M F (g / mole), and the atomic weight of oxygen is M O (g / mole),
[0198] M=(s×M A +t×M B +u×M F -u / 2×M O ) / (s+t).
[0199] For example, the molar molecular weight M of the comparative example A described later (the contents expressed in mol % in the oxide-based glass composition are: P2O5=53.59, Li2O=19.30, CuO=27.11) can be used.
[0200] Formula weight of P2O5: 141.94 (g / mole)
[0201] Formula weight of Li2O: 29.88 (g / mole)
[0202] Formula weight of CuO: 79.55 (g / mole),
[0203] It was calculated that M = (53.59 x 141.94 + 19.30 x 29.88 + 27.11 x 79.55) / (53.59 + 19.30 + 27.11) = 103.40 (g / mole).
[0204] The present inventors have repeatedly conducted in-depth studies and have newly discovered the following results: if the O / P ratio is reduced in a glass mainly composed of O ions as anions, the absorption of CuO in the red region shifts to the long wavelength side, thereby suppressing the reduction in transmittance in the red region and increasing the CuO content. In addition, the present inventors have newly discovered that there is a good correlation between the O / P ratio and the CuO content for achieving a given half value with a given thickness. For glass 2 with an O / P ratio in the range described above, the lower limit of the CuO content (α1, α2) is specified by formula 1, and for glass 5, the lower limit of the CuO content (α1, α2) is specified by formula 5. In addition, for glasses with an O / P ratio in the range described above, the CuO content per molar volume of glass is specified by formula 2, and for glass 6, the CuO content per molar volume of glass is specified by formula 6.
[0205] In Glass 3, the CuO content is specified based on A1 calculated by the following formula 3, and A1 is 2500 or more.
[0206] (Formula 3)
[0207] A1={O(P)-O(others)}×Cu
[0208] In Formula 3, O(P) represents the amount of oxygen in the oxide that constitutes the P ion in the glass composition on an oxide basis, O(others) represents the amount of oxygen in the glass composition on an oxide basis after removing the above O(P) from the amount of oxygen in the oxide of the main cations shown previously constituting Glass 3, and Cu represents the CuO content on a molar basis in the glass composition on an oxide basis.
[0209] "O(P)" in Formula 3 is calculated as follows.
[0210] When the P2O5 content in the oxide-based glass composition (molar basis) is M mol%, O(P) is calculated using "O(P)=M×5" using the number of oxygen contained in the chemical formula of P2O5: 5.
[0211] Similarly, for the main cations other than P ions, the amount of oxygen constituting the oxide of each cation is calculated using the value of the content in terms of oxide in the glass composition (molar basis) based on the oxide and the amount of oxygen contained in the oxide formed by each cation in a formal valence state.
[0212] “O(others)” is calculated from the value obtained by subtracting O(P) from the total amount of oxygen calculated for the oxides of the main cations in this manner.
[0213] When the CuO content in the oxide-based glass composition (molar basis) is N mol %, “A1” is calculated as A1={O(P)−O(others)}×N.
[0214] As described above, the inventors have newly discovered the following result: if the O / P ratio is reduced in a glass mainly composed of O ions as anions, the absorption of CuO in the red region shifts to the long wavelength side, thereby suppressing the decrease in transmittance in the red region and increasing the CuO content. In addition, the following new insights have been obtained: by forming chemical species other than PO coordinated with CuO by chemical species with smaller ion radius and smaller valence, according to the following 1) and 2), the transmittance in the visible region (purple region to red region) can be improved. With respect to glass 3, based on the above insights, the CuO content is specified based on A1 calculated by formula 3.
[0215] 1) By making the 2+ The absorption of longer wavelengths can increase the transmittance in the red region.
[0216] 2) Since the glass can be made into a liquid phase at low temperature, the absorption of Cu in the purple region around 400 nm can be suppressed. + The production of.
[0217] Regarding glass 3, from the viewpoint of achieving both an improvement in transmittance in the visible region and an improvement in near infrared shielding capability, A1 is 2500 or more, preferably 2800 or more, and preferably 2900 or more, 3000 or more, 3100 or more, 3200 or more, 3300 or more, 3400 or more, 3500 or more, 3600 or more, 3700 or more, 3800 or more, 3900 or more, 4000 or more, 4100 or more, 4200 or more, 4300 or more. , 4400 or more, 4500 or more, 4600 or more, 4700 or more, 4800 or more, 4900 or more, 5000 or more, 5100 or more, 5200 or more, 5300 or more, 5400 or more, 5500 or more, 5600 or more, 5700 or more, 5800 or more, 5900 or more, 6000 or more, 6100 or more, 6200 or more, 6300 or more, 6400 or more, and 6500 or more are more preferred. On the other hand, from the viewpoint of further suppressing the decrease in thermal stability of the glass caused by the large amount of Cu and O, the decrease in transmittance at the wavelength of the desired half value, and / or the decrease in thermal stability or weather resistance of the glass caused by too little O (others), A1 is preferably 20000 or less, more preferably 19000 or less, 18000 or less, 17000 or less, 16000 or less, 15000 or less, 14000 or less, 13000 or less, 12000 or less, 11000 or less, 10000 or less, 9000 or less, or 8000 or less. It should be noted that in order to achieve the desired half value with a thinner thickness, there is a tendency to prefer a larger value.
[0218] In Glass 4, the CuO content is specified based on A2 calculated by the following formula 4, and A2 is 700 or more.
[0219] (Formula 4)
[0220] A2={O(P)-O(others)}×C
[0221] In Formula 4, C is the CuO content per molar volume of glass (unit: millimole / cc). O(P) represents the amount of oxygen in the oxide constituting the P ion in the glass composition based on the oxide, and O(others) represents the amount of oxygen after removing the above O(P) from the amount of oxygen in the oxide constituting the above main cation in the glass composition based on the oxide.
[0222] Regarding glass 4, from the viewpoint of achieving both an improvement in transmittance in the visible region and an improvement in near infrared shielding capability, A2 is 700 or more, preferably 800 or more, and more preferably in the order of 850 or more, 890 or more, 1000 or more, 1100 or more, 1200 or more, 1300 or more, 1400 or more, 1500 or more, 1600 or more, 1700 or more, and 1800 or more. On the other hand, from the viewpoint of further suppressing a decrease in thermal stability of the glass due to a large amount of Cu and O, a decrease in transmittance at a desired half-value wavelength, and / or a decrease in thermal stability or weather resistance of the glass due to too little O (others), A2 is preferably 5000 or less, more preferably 4000 or less, 3500 or less, 3000 or less, 2500 or less, and 2000 or less. It should be noted that in order to achieve a desired half-value of transmittance with a thinner thickness, there is a tendency to prefer a larger value.
[0223] In addition, in Glass 5, the CuO content is α2% or more. α2 is a value calculated by the following formula 5.
[0224] (Formula 5)
[0225] α2=76522×exp(-2.855×R)
[0226] In Formula 5, R is the O / P ratio.
[0227] In addition, regarding Glass 6, the lower limit of the CuO content is defined by the following Formula 6 based on the CuO content per molar volume of glass.
[0228] (Formula 6)
[0229] C-3478×exp(-2.278×R)≥0
[0230] In Formula 6, C is the CuO content per molar volume of glass (unit: mmol / cc), and R is the O / P ratio.
[0231] The CuO content of glasses 1 to 6 is preferably 4.0% or more in the glass composition based on oxide (molar basis), and is more preferably 5.0% or more, 6.0% or more, 7.0% or more, 7.5% or more, 8.0% or more, 8.5% or more, 9.0% or more, 9.5% or more, 10.0% or more, 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more in this order. From the viewpoint of leaving room for introducing glass-forming components and maintaining the thermal stability of the glass, the CuO content is preferably 48.0% or less, and more preferably 47.0% or less, 46.0% or less, 45.0% or less, 44.0% or less, 43.5% or less, 43.0% or less, 42.5% or less, 42.0% or less, 41.5% or less, 41.0% or less, 40.5% or less, 40.0% or less, 39.5% or less, 39.0% or less, 38.5% or less, 38.0% or less, 37.5% or less, 37.0% or less, 36.5% or less, 36.0% or less, 35.5% or less, 35.0% or less, 34.5% or less, 34.0% or less, 33.5% or less, 33.0% or less, 32.5% or less, 32.0% or less, 31.5% or less, and 31.0% or less.
[0232] As the transmittance characteristics converted to a thickness of 0.11 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the CuO content in the oxide-based glass composition (molar basis) is preferably 15.0% or more, and more preferably 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more.
[0233] As the transmittance characteristics converted to a thickness of 0.21 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% is T50 is in the range of 600nm to 650nm, and the CuO content in the oxide-based glass composition (molar basis) is preferably 10.0% or more, and more preferably 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more in the order of more preferably.
[0234] As the transmittance characteristics converted to a thickness of 0.25 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the CuO content in the oxide-based glass composition (molar basis) is preferably 10.0% or more, and more preferably 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more in the order of more preferably.
[0235] On the other hand, regarding the transmittance characteristics converted to a thickness of 0.25 mm, if the CuO content becomes large, the wavelength λ at which the external transmittance including the reflection loss reaches 50% is T 50 may be lower than 600nm, and therefore, the CuO content is preferably less than 35.0%, and more preferably in the order of less than 34.0%, less than 33.0%, less than 32.0%, less than 31.0%, less than 30.0%, less than 29.5%, less than 29.0%, less than 28.5%, less than 28.0%, less than 27.5%, less than 27.0%, less than 26.5%, less than 26.0%, less than 25.5%, less than 25.0%, less than 24.5%, less than 24.0%, less than 23.5%, less than 23.0%, less than 22.5%, less than 22.0%, less than 21.5%, less than 21.0%, less than 20.5%, and less than 20.0%.
[0236] In order to make the external transmittance including reflection loss reach 50% at wavelengths above 550nm, the wavelength λ TThe thickness of the glass having an oxide content of 50 to 645 nm is less than 0.25 mm, and the CuO content in the glass composition based on oxide (molar basis) is preferably 10.0% or more, and more preferably 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, and 20.0% or more.
[0237] In order to make the external transmittance including reflection loss reach 50% at wavelengths above 550nm, the wavelength λ T The thickness of the glass having an oxide content of 50 or more and a molecular weight of 633 nm or more is less than 0.25 mm, and the CuO content in the glass composition based on oxide (molar basis) is preferably 10.5% or more, and more preferably 11.0% or more, 11.5% or more, 12.0% or more, 12.5% or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more.
[0238] In glass 2 and glass 4, the value of C is preferably greater than 3.0, and more preferably in the order of greater than 3.1, greater than 3.3, greater than 3.5, greater than 3.7, greater than 3.9, greater than 4.0, greater than 4.1, greater than 4.2, greater than 4.3, greater than 4.4, greater than 4.5, greater than 4.6, greater than 4.7, greater than 4.8, greater than 4.9, greater than 5.0, greater than 5.1, greater than 5.2, greater than 5.3, greater than 5.4, and greater than 5.5. From the viewpoint of leaving room for the introduction of glass-forming components and maintaining the thermal stability of the glass, the value of C is preferably 16.0 or less, and further preferably 15.0 or less, 14.0 or less, 13.5 or less, 13.0 or less, 12.5 or less, 12.0 or less, 11.9 or less, 11.8 or less, 11.7 or less, 11.6 or less, 11.5 or less, 11.4 or less, 11.3 or less, 11.2 or less, 11.1 or less, 11.0 or less, 10. The order of less than 9, less than 10.8, less than 10.7, less than 10.6, less than 10.5, less than 10.4, less than 10.3, less than 10.2, less than 10.1, less than 10.0, less than 9.9, less than 9.8, less than 9.7, less than 9.6, less than 9.5, less than 9.4, less than 9.3, less than 9.2, less than 9.1, less than 9.0, less than 8.9, less than 8.8, less than 8.7, less than 8.6, and less than 8.5 is more preferred.
[0239] In glasses 1 to 6, the CuO content may be α3% or more. α3 is a value calculated by the following formula 7.
[0240] (Formula 7)
[0241] α3=(70400×0.25 / d)×exp(-2.855×R)
[0242] In formula 7, R is the O / P ratio. d can take a value greater than 0 and less than 0.25. For example, d can be 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, etc. However, the value of d is not limited to these values. In order to achieve the desired transmittance half value with a thinner thickness, there is a tendency to prefer a smaller value of d.
[0243] For example, when d=0.11, the CuO content can be α3% or more, and α3 is calculated by the following formula.
[0244] α3=(70400×0.25 / 0.11)×exp(-2.855×R)
[0245] In glass, when the thickness of the glass when the external transmittance for light of wavelength 633 nm reaches 50% is D (mm), in one embodiment, d=D can be satisfied in the above formula 7. In this case, α3 is calculated by the following formula.
[0246] α3=(70400×0.25 / D)×exp(-2.855×R)
[0247] Regarding Glasses 1 to 6, the lower limit of the CuO content may be a value defined by the following formula 8 based on the CuO content per molar volume of glass.
[0248] (Formula 8)
[0249] C-3200×0.25 / d×exp(-2.855×R)≥0
[0250] In formula 8, d can take a value greater than 0 and less than 0.25. For example, d can be 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, etc. However, the value of d is not limited to these values. In order to achieve the desired transmittance half value with a thinner thickness, there is a tendency to prefer a smaller value of d.
[0251] For example, when d=0.11, Formula 8 is as follows.
[0252] C-3300×0.25 / 0.11×exp(-2.855×R)≥0
[0253] In glass, when the thickness of the glass when the external transmittance for light of a wavelength of 633 nm reaches 50% is D (mm), in one embodiment, d=D can be satisfied in the above formula 8.
[0254] Regarding the CuO content, each of the glasses 1 to 6 may satisfy one or more of the regulations in the formula related to the other glasses.
[0255] Glasses 1 to 6 contain P ions as essential cations. As described above, from the perspective of achieving both improved transmittance in the visible region and improved near-infrared shielding capability, a lower O / P ratio is preferred. In order to reduce the O / P ratio, it is preferred to increase the P2O5 content. From this point of view, the P2O5 content in the oxide-based glass composition (molar basis) is preferably 33.0% or more, and more preferably 34.0% or more, 35.0% or more, 36.0% or more, 37.0% or more, 38.0% or more, 39.0% or more, 40.0% or more, 40.5% or more, 41.0% or more, 41.5% or more, 42.0% or more, 42.5% or more, 43.0% or more, 43.5% or more, 44.0% or more, 44.5% or more, 45.0% or more, 45.5% or more, 46.0% or more, 46.5% or more, 47.0% or more, 47.5% or more, 48.0% or more, 48.5% or more, 49.0% or more, 49.5% or more, and 50.0% or more. P2O5 itself is a component that does not have near-infrared absorption capability. Therefore, from the viewpoint of increasing the content of CuO having near-infrared absorption capability, the P2O5 content is preferably 72.0% or less, and more preferably in the order of 71.0% or less, 70.0% or less, 69.5% or less, 69.0% or less, 68.5% or less, 68.0% or less, 67.5% or less, 67.0% or less, 66.5% or less, 66.0% or less, 65.5% or less, 65.0% or less, 64.5% or less, 64.0% or less, 63.5% or less, 63.0% or less, 62.5% or less, 62.0% or less, 61.5% or less, 61.0% or less, 60.5% or less, and 60.0% or less. In addition, from the viewpoint of further suppressing the decrease in weather resistance and / or the viewpoint of suppressing the decrease in solubility, it is also preferred that the P2O5 content is less than the above-mentioned value.
[0256] In order to obtain the desired transmittance characteristics, it is desirable that the glass composition of the above-mentioned glass on an oxide basis mainly consists of P2O5, Li2O and CuO. In view of this point, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) is preferably 50.0% or more, and more preferably in the order of 55.0% or more, 60.0% or more, 65.0% or more, 70.0% or more, 75.0% or more, 80.0% or more, 83.0% or more, 86.0% or more, 88.0% or more, and 90.0% or more. The above-mentioned glass contains P ions, Li ions and Cu ions as essential cations, and further contains one or more cations selected from the group of main cations in order to obtain the thermal stability of the glass and / or the chemical durability of the glass. Therefore, the total content (P2O5+Li2O+CuO) is less than 100%, preferably less than 99.9%, and more preferably less than 99.8%, less than 99.7%, less than 99.6%, less than 99.5%, less than 99.4%, less than 99.2%, less than 99.0%, less than 98.0%, less than 97.0%, less than 96.0%, less than 95.0%, less than 94.0%, less than 93.0%, less than 92.0%, less than 91.0%, less than 90.0%, less than 89.0%, less than 88.0%, less than 87.0%, less than 86.0%, and less than 85.0%.
[0257] In one embodiment, as the transmittance characteristic converted to a thickness of 0.11 mm, the wavelength λ at which the external transmittance including the reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably 84.0% or more, and more preferably 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more.
[0258] As the transmittance characteristics converted to a thickness of 0.21 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably 80.0% or more, and more preferably 81.0% or more, 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more.
[0259] As the transmittance characteristics converted to a thickness of 0.25 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably 75.0% or more, and more preferably 76.0% or more, 77.0% or more, 78.0% or more, 79.0% or more, 80.0% or more, 81.0% or more, 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more in the order of more preferred contents.
[0260] In order to make the external transmittance including reflection loss reach 50% at wavelengths above 550nm, the wavelength λ T The thickness of the glass reaching 50 to 645 nm is less than 0.25 mm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably more than 80.0%, and more preferably in the order of more than 81.0%, more than 82.0%, more than 83.0%, more than 84.0%, more than 85.0%, more than 86.0%, more than 87.0%, more than 88.0%, more than 89.0%, and more than 90.0%.
[0261] In order to make the external transmittance including reflection loss reach 50% at wavelengths above 550nm, the wavelength λ T The thickness of the glass reaching 50 to 633 nm is less than 0.25 mm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably more than 81.0%, and more preferably in the order of more than 82.0%, more than 83.0%, more than 84.0%, more than 85.0%, more than 86.0%, more than 87.0%, more than 88.0%, more than 89.0%, and more than 90.0%.
[0262] As glass that conforms to one embodiment described above, glasses of Examples 1 to 60 described below are mentioned.
[0263] On the other hand, as another embodiment, for glass in which the molar ratio of the total content of MgO, CaO, SrO, BaO and ZnO (MgO+CaO+SrO+BaO+ZnO) to the total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) ((MgO+CaO+SrO+BaO+ZnO) / (Li2O+Na2O+K2O)) is 2.0 or more, as the transmittance characteristics converted to a thickness of 0.11 mm, in order to make the external transmittance including the reflection loss reach 50% at a wavelength λ T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably above 65.0%, and more preferably above 66.0%, above 67.0%, above 68.0%, above 69.0%, and above 70.0% in the order of above.
[0264] Regarding the above-mentioned other aspect, as the transmittance characteristic converted to a thickness of 0.21 mm, the wavelength λ at which the external transmittance including the reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably above 60.0%, and more preferably above 61.0%, above 62.0%, above 63.0%, above 64.0%, and above 65.0% in the order of above.
[0265] Regarding the above-mentioned other aspect, as the transmittance characteristic converted to a thickness of 0.25 mm, the wavelength λ at which the external transmittance including the reflection loss reaches 50% is T 50 is in the range of 600nm to 650nm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably above 55.0%, and more preferably above 56.0%, above 57.0%, above 58.0%, above 59.0%, and above 60.0% in the order of above.
[0266] Regarding the above-mentioned other embodiment, in order to make the external transmittance including reflection loss reach 50% at a wavelength λ of 550 nm or more T The thickness of the glass reaching 50 to 645 nm is less than 0.25 mm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably greater than 60.0%, and more preferably greater than 61.0%, greater than 62.0%, greater than 63.0%, greater than 64.0%, and greater than 65.0% in the order of greater than 60.0%.
[0267] Regarding the above-mentioned other embodiment, in order to make the external transmittance including reflection loss reach 50% at a wavelength λ of 550 nm or more T The thickness of the glass reaching 50 to 633 nm is less than 0.25 mm, and the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the oxide-based glass composition (molar basis) is preferably greater than 61.0%, and more preferably greater than 62.0%, greater than 63.0%, greater than 64.0%, greater than 65.0%, and greater than 66.0% in the order of greater than 66.0%.
[0268] Examples of glass that conforms to another embodiment described above include Examples 61 to 66 described below.
[0269] For glasses 3 and 4, the group of main cations described above includes B ions and Si ions. On the other hand, for glasses 1, 2, 5, and 6, the group of main cations described above does not include B ions and Si ions that tend to increase the melting temperature. In one embodiment, from the viewpoint of improving the near-infrared shielding ability of the glass and improving the transmittance in the visible region, glasses 1 to 6 may be glasses containing one or both of B ions and Si ions that tend to shift the half-value to the short wavelength side, and in another embodiment, may be glasses containing neither B ions nor Si ions.
[0270] Regarding glass 1 and glass 2, from the viewpoint of improving the transmittance in the visible region, in the oxide-based glass composition (molar basis), the total content of B2O3 and SiO2 (B2O3+SiO2) is less than 3.0%, preferably less than 2.5%, and more preferably less than 2.0%, less than 1.5%, less than 1.0%, and less than 0.5%.
[0271] Regarding glasses 3 to 6, from the viewpoint of further improving the transmittance in the visible region, in the oxide-based glass composition (molar basis), the total content of B2O3 and SiO2 (B2O3+SiO2) is preferably less than 3.0%, and more preferably less than 2.5%, less than 2.0%, less than 1.5%, less than 1.0%, and less than 0.5%.
[0272] In glasses 1 to 6, the total content of B2O3 and SiO2 (B2O3+SiO2) may be 0%, 0% or more, or more than 0%.
[0273] In glasses 1 to 6, from the viewpoint of further improving the transmittance in the visible region, the B2O3 content is preferably 3.0% or less, and more preferably 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, and 0.5% or less. The B2O3 content may be 0%.
[0274] On the other hand, regarding glasses 1 to 6, when the glasses are roughly melted in a quartz crucible in order to promote homogenization of the glasses, the SiO2 content is preferably more than 0%, and more preferably in the order of 0.01% or more, 0.02% or more, 0.03% or more, 0.04% or more, 0.05% or more, 0.1% or more, 0.2% or more, and 0.3% or more. However, the introduction of excessive SiO2 into the glass tends to reduce the optical homogeneity of the glass. From this point of view, in glasses 1 to 6, the SiO2 content is preferably 2.0% or less, and more preferably in the order of 1.4% or less, 0.9% or less, 0.8% or less, 0.6% or less, and 0.4% or less.
[0275] Glasses 1 to 6 contain Li ions as essential cations. Li2O has a higher ability to maintain the absorption of CuO in the long wavelength range than various glass components, and has less adverse effects on weather resistance. From this point of view, the Li2O content is preferably 0.1% or more, and more preferably in the order of 0.5% or more, 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, 7.0% or more, 7.5% or more, and 8.0% or more. On the other hand, from the viewpoint of ensuring the thermal stability of the glass and / or further suppressing the decrease in weather resistance, the Li2O content is preferably 35.0% or less, and more preferably 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.5% or less, 29.0% or less, 28.5% or less, 28.0% or less, 27.5% or less, 27.0% or less, 26.5% or less, 26.0% or less, 25.5% or less, 25.0% or less, 24.5% or less, 24.0% or less, 23.5% or less, 23.0% or less, 22.5% or less, 22.0% or less, 21.5% or less, 21.0% or less, 20.5% or less, and 20.0% or less.
[0276] In glasses 1 to 6, from the viewpoint of improving solubility and improving transmittance in the visible region, the total content of MgO and Al2O3 (MgO+Al2O3) is 8.0% or less, preferably 7.5% or less, and more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.8% or less, 1.6% or less, 1.5% or less, and 1.4% or less in this order, and may also be 0%. On the other hand, from the perspective of improving the weather resistance of glass and improving the mechanical strength of glass, the total content of MgO and Al2O3 (MgO+Al2O3) can exceed 0%, preferably above 0.1%, and more preferably in the order of above 0.2%, above 0.3%, above 0.4%, above 0.5%, above 0.6%, above 0.7%, above 0.8%, above 0.9%, above 1.0%, above 1.1%, and above 1.3%.
[0277] Al2O3 is a component that can contribute to particularly improving weather resistance. The Al2O3 content can be 0%, 0% or more, or more than 0%. From the perspective of improving weather resistance, it is preferably 0.1% or more, and more preferably in the order of 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.9%, 1.1%, 1.3%, and 1.5%. On the other hand, from the perspective of further suppressing the decrease in transmittance in the visible region, the Al2O3 content is preferably 8.0% or less, and more preferably in the order of 7.5%, 7.0%, 6.0%, 5.5%, 5.0%, 4.5%, 4.0%, 3.5%, 3.0%, and 2.5%. In one embodiment, from the viewpoint of giving priority to improving the near-infrared absorption characteristics over maintaining the weather resistance of the glass, being able to further improve the transmittance in the visible region by suppressing the absorption of CuO from shifting to the short wavelength side, and improving the near-infrared absorption characteristics, the Al2O3 content is preferably less than 2.0%, and is more preferably in the order of less than 1.9%, less than 1.8%, less than 1.7%, less than 1.6%, less than 1.5%, less than 1.4%, less than 1.3%, less than 1.2%, less than 1.1%, less than 1.0%, less than 0.9%, less than 0.8%, less than 0.7%, less than 0.6%, and less than 0.5%.
[0278] MgO is a component that can be appropriately added based on the reason of adjusting the thermal stability of the glass, but since it can shift the absorption of CuO to the short wavelength side, there is a tendency that it is difficult to increase the CuO content. In addition, the solubility of the glass tends to decrease with the increase of the MgO content. From these viewpoints, the MgO content is preferably 9.0% or less, and more preferably in the order of 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, and 2.0% or less. The MgO content can also be 0%. In one embodiment, from the viewpoint of improving the mechanical strength of the glass, the MgO content can exceed 0%, preferably 0.5% or more, and more preferably 1.0% or more.
[0279] La2O3 is a component that can help improve weather resistance without damaging the near-infrared absorption characteristics of the glass. The La2O3 content is preferably 0.10% or more, and more preferably in the order of 0.15% or more, 0.18% or more, and 0.21% or more. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible region, the La2O3 content is preferably 8.0% or less, and more preferably in the order of 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less.
[0280] Y2O3 is also a component that can help improve weather resistance without damaging the near-infrared absorption characteristics of glass. The Y2O3 content is preferably 0.10% or more, and is more preferably in the order of 0.15% or more, 0.20% or more, 0.25% or more, 0.30% or more, 0.35% or more, 0.40% or more, 0.45% or more, and 0.50% or more. On the other hand, from the perspective of further suppressing the decrease in transmittance in the visible region, the Y2O3 content is preferably 8.0% or less, and is more preferably in the order of 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less. It should be noted that Y2O3 can also be introduced from the perspective of increasing the molar volume of the glass without increasing the specific gravity of the glass.
[0281] Gd2O3 is also a component that can help improve weather resistance. The Gd2O3 content is preferably 0.10% or more, and more preferably in the order of 0.15% or more, 0.18% or more, and 0.21% or more. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible region, the Gd2O3 content is preferably 8.0% or less, and more preferably in the order of 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less.
[0282] It should be noted that the oxide-based glass composition may contain one or more of the rare earth oxides other than the above, such as Lu2O3 and Sc2O3, or may not contain them. These components are generally expensive, so the content of rare earth oxides other than La2O3, Y2O3 and Gd2O3 (their total content when two or more are included) is preferably 2.5% or less, preferably 1.5% or less, 1.0% or less, 0.5% or less, and may also be 0%.
[0283] In glasses 1 to 6, from the perspective of improving weather resistance, the total content of Al2O3, La2O3, Y2O3 and Gd2O3 (Al2O3+La2O3+Y2O3+Gd2O3) is preferably above 0.1%, and more preferably above 0.15%, above 0.20%, above 0.25%, above 0.30%, above 0.35%, above 0.40%, above 0.45%, and above 0.50%. On the other hand, from the perspective of ensuring the thermal stability of the glass and / or lowering the melting temperature, the total content (Al2O3+La2O3+Y2O3+Gd2O3) is preferably less than 8.0%, and more preferably less than 7.0%, less than 6.5%, less than 6.0%, less than 5.5%, less than 5.0%, less than 4.5%, less than 4.0%, less than 3.5%, less than 3.0%, less than 2.5%, less than 2.0%, less than 1.5%, and less than 1.0%.
[0284] There is a tendency that the cations with a formal valence of +2 have the following tendency: when observing the glass composition as a whole, it is difficult to play a prominent role in terms of the improvement of the transmittance in the visible region and the weather resistance. Therefore, the molar ratio ((MgO+CaO+SrO+BaO) / Li2O) of the total content of MgO, CaO, SrO and BaO as oxides of cations with a formal valence of +2 to the content of the oxide Li2O of Li ions as essential cations is preferably 2.0 or less, more preferably 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. As described later, the above-mentioned components are arbitrary components that can be used when adjusting the half value together with a part of the alkali component.
[0285] In addition, regarding the total content of MgO, CaO, SrO, BaO and ZnO as oxides of cations with a formal valence of +2, from the viewpoint of improving the transmittance in the visible region, the molar ratio ((MgO+CaO+SrO+BaO+ZnO) / Li2O) relative to the content of the oxide Li2O of Li ions as essential cations is preferably 2.0 or less, and more preferably 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. On the other hand, from the viewpoint of improving weather resistance, ((MgO+CaO+SrO+BaO+ZnO) / Li2O) is preferably 2.0 or more, and more preferably in the order of 2.5 or more, 3.0 or more, 3.5 or more, and 4.0 or more. As described later, the above components are arbitrary components that can be used when adjusting the half value together with a part of the alkali component.
[0286] The BaO content is 0%, or may be 0% or more or more than 0%. BaO is a component that improves weather resistance by introducing a certain amount, and the change in T600 caused by the introduction is small. T600 will be described later. BaO can be added for the purpose of improving the thermal stability of the glass and adjusting the solubility. In addition, BaO can also be used to adjust the concentration of CuO. The BaO content is preferably 0.5% or more, and more preferably in the order of 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more. However, there is a tendency to reduce T400 due to excessive introduction. T400 will be described later. From the above viewpoints, the BaO content is preferably 36.0% or less, and more preferably 35.0% or less, 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less in this order.
[0287] The SrO content is 0%, and may be 0% or more or exceed 0%. Like BaO, SrO is a component that is relatively difficult to reduce weather resistance, and is a component that can be appropriately added for reasons such as adjusting the thermal stability of the glass. SrO can also be used to adjust the concentration of CuO. The SrO content is preferably 0.5% or more, and more preferably in the order of 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more. However, there is a tendency for T400 to decrease due to excessive introduction, and therefore the SrO content is preferably 30.0% or less, and more preferably 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less in this order.
[0288] The CaO content is 0%, and may be 0% or more or more than 0%. CaO is a component that is relatively difficult to reduce weather resistance, and is also a component that can be appropriately added for reasons such as thermal stability of the glass. CaO can also be used to adjust the concentration of CuO. The CaO content is preferably 0.5% or more, preferably 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, 7.0% or more. However, there is a tendency for T400 to decrease due to excessive introduction, and therefore the CaO content is preferably 30.0% or less, and more preferably 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less in this order.
[0289] Among the cations included in the above-described group of main cations, Na ions, K ions, and Zn ions tend to deteriorate the weather resistance of glass, and therefore, it is difficult to freely use them in place of Li ions, which are essential cations. In addition to this point, from the perspective of improving the transmittance in the visible region or the near-infrared region, in glasses 1 to 6, the ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is preferably 2.4 or less, more preferably 2.3 or less, and is more preferably in the order of 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, and 0.05 or less, and can also be set to 0.00. On the other hand, from the perspective of reducing the raw material cost of glass, the molar ratio ((Na2O+K2O+ZnO) / Li2O) can be 0, above 0 or above 0. From the perspective of promoting the reduction of Tg and Tm described later by mixing multiple components, it is preferably above 0.05, and can also be above 0.1, above 0.2, or above 0.3.
[0290] In addition, the more Na ions, K ions and Zn ions are present, the more difficult it is to introduce a large amount of P2O5 to maintain weather resistance, and as a result, the more difficult it is to introduce a desired amount of P2O5. From the above viewpoints and the viewpoint of suppressing the reduction of weather resistance as described above, the total content of Na2O, K2O and ZnO (Na2O+K2O+ZnO) is preferably 30.0% or less, and more preferably in the order of 25.0% or less, 20.0% or less, 15.0% or less, 12.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, and 1.0% or less. The above total content may also be 0%. On the other hand, from the viewpoint of reducing the raw material cost of glass, the total content (Na2O+K2O+ZnO) may be 1.0% or more, 2.0% or more, 3.0% or more, or 5.0% or more.
[0291] The Na2O content can be 0%, 0% or more, or more than 0%. Na2O also has a tendency to reduce heat resistance due to excessive introduction. Therefore, the Na2O content is preferably less than 20.0%, and is more preferably in the order of less than 19.0%, less than 18.0%, less than 17.0%, less than 16.0%, less than 15.0%, less than 14.0%, less than 13.0%, less than 12.0%, less than 11.0%, less than 10.0%, less than 9.0%, and less than 8.0%. On the other hand, Na2O is an easily available and low-cost raw material, and can be appropriately added to improve solubility. Therefore, the Na2O content can be, for example, more than 0.5%, and can also be more than 1.0%, more than 1.5%, more than 2.0%, more than 2.5%, more than 3.0%, more than 3.5%, more than 4.0%, and more than 5.0%.
[0292] The K2O content can be 0%, 0% or more, or more than 0%. K2O also tends to reduce weather resistance due to excessive introduction. In addition, there is a tendency to shorten the wavelength of absorption of CuO, and it is expected that it is not actively introduced. From these viewpoints, the K2O content is preferably less than 20.0%, and is more preferably in the order of less than 19.0%, less than 18.0%, less than 17.0%, less than 16.0%, less than 15.0%, less than 14.0%, less than 13.0%, less than 12.0%, less than 11.0%, less than 10.0%, less than 9.0%, and less than 8.0%. On the other hand, K2O can be appropriately added to improve the solubility of the glass. From this viewpoint, the K2O content is preferably more than 0.2%, and is more preferably in the order of more than 0.5%, more than 1.0%, more than 1.5%, more than 2.0%, more than 2.5%, more than 3.0%, more than 3.5%, more than 4.0%, and more than 5.0%.
[0293] The Cs2O content can be 0%, 0% or more, or more than 0%. Cs2O also tends to reduce weather resistance, so it is not expected to be actively introduced. The Cs2O content is more preferably 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, and 6.0% or less. On the other hand, in order to adjust thermal stability and solubility, the Cs2O content can be set to 0.5% or more, and can also be set to 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 5.0%, 6.0%, 7.5%, 8.0%, 9.0%, 10.0%, 11.0%, 10 ...
[0294] From the viewpoint of improving the solubility of glass, the total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) is preferably 1.8% or more, and more preferably 2.1% or more, 2.3% or more, 2.5% or more, 3.5% or more, 4.5% or more, 5.5% or more, 6.5% or more, 7.5% or more, 8.5% or more, 9.5% or more, 10.0% or more, and 10.5% or more.
[0295] On the other hand, from the viewpoint of further suppressing the decrease in weather resistance, the total content (Li2O+Na2O+K2O) is preferably 35.0% or less, and more preferably 33.5%, 32.5%, 31.5%, 30.5%, 29.5%, 28.5%, 27.5%, 26.5%, 25.5%, 24.5%, 23.5%, 21.5%, 20.5%, 19.5%, 18.5%, 17.5%, 16.6%, 15.5%, 14.5%, and 13.5% or less. From the viewpoint of avoiding the increase in the expansion and contraction of the glass due to the increase in the thermal expansion coefficient and the stress applied to the glass when the volume change of the glass is restricted by other components, resulting in the formation of cracks and cracks in the glass, the total content (Li2O+Na2O+K2O) is also preferably less than the above value.
[0296] From the viewpoint of suppressing the deliquescent property of the glass, the total content of Na2O and K2O (Na2O+K2O) is preferably 30.0% or less, and more preferably 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, and 0.5% or less in this order. By setting the total content of Na2O and K2O (Na2O+K2O) to 0%, it is possible to obtain a glass with further suppressed deliquescent properties. On the other hand, from the viewpoint of suppressing the solubility of the glass, suppressing the decrease in T600, and suppressing the raw material cost of the glass, the total content (Na2O+K2O) can be set to 1.0% or more, and further can be set to 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, 8.0% or more, 9.0% or more, 10.0% or more, 11.0% or more, 12.0% or more, 13.0% or more, 14.0% or more, or 15.0% or more.
[0297] When adjusting the thickness of the glass, CuO may be replaced with other components. In this case, by making the glass such that the total content of Na2O, K2O, CaO, SrO and BaO (Na2O+K2O+CaO+SrO+BaO) is 0% or more, the CuO concentration can be adjusted without significantly changing the position of near-infrared absorption. The total content (Na2O+K2O+CaO+SrO+BaO) is preferably 0.5% or more, and more preferably in the order of 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more. However, there is a tendency for T400 to decrease due to excessive introduction, and therefore, the total content (Na2O+K2O+CaO+SrO+BaO) is preferably 36.0% or less, and more preferably 35.0% or less, 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less in this order. From the viewpoint of maximizing the near-infrared absorption characteristics of the glass, the total content (Na2O+K2O+CaO+SrO+BaO) may be 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, or 4.0% or less.
[0298] Regarding weather resistance, one or both of inhibiting the deliquescence of glass and inhibiting the generation of precipitates on the glass surface in high temperature and high humidity can be used as an index of weather resistance. This point will be further described later. In order to further improve weather resistance, it is preferred to introduce Al2O3, and then preferably introduce one or more of Y2O3, La2O3 and Gd2O3. In addition, the above-mentioned weather resistance can be improved by introducing more BaO. From the perspective of improving weather resistance, it is necessary to introduce more SrO and CaO. Therefore, the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" (unit: mole %) is preferably 0% or more, more preferably more than 0%, preferably set to 0.5% or more, 1.0% or more, 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, 8.0% or more. In addition, when the weather resistance and mechanical strength of the glass are emphasized, the order of 9.0% or more, 10.0% or more, 11.0% or more, 12.0% or more, 13.0% or more, 14.0% or more, 15.0% or more, 16.0% or more, 17.0% or more, 18.0% or more, and 19.0% or more is more preferred. In "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)", "Al2O3" is the Al2O3 content, "Y2O3" is the Y2O3 content, "La2O3" is the La2O3 content, "Gd2O3" is the Gd2O3 content, "BaO" is the BaO content, "CaO" is the CaO content, and "SrO" is the SrO content. That is, "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is the sum of the value calculated by multiplying the Al2O3 content by 3 times, the value calculated by 1 / 3 of the Y2O3 content, La2O3 content, Gd2O3 content, and BaO content, and the value calculated by 1 / 6 of the total of the CaO content and the SrO content, and the values calculated in this way are expressed with % (molar %) as the unit.
[0299] On the other hand, if the value of "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is increased excessively, the solubility of the glass tends to deteriorate, and the position of near-infrared absorption tends to shift to the visible light side. Therefore, the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is preferably less than 40.0%, and more preferably less than 37.0%, less than 35.0%, less than 33.0%, less than 32.0%, less than 30.0%, less than 28.0%, less than 26.0%, less than 25.0%, less than 24.0%, less than 23.0%, less than 22.0%, and less than 21.0% in this order.
[0300] For the total content of P2O5, Li2O and CuO, the ratio of the values calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)", that is, "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6) / (P2O5+Li2O+CuO)" can be 0.0 or more. It is desirable to introduce a certain amount or more of components selected from Al2O3, Y2O3, La2O3, Gd2O3, BaO, CaO and SrO into P2O5, Li2O and CuO as essential components. Therefore, the above ratio is preferably 0.01 or more, and more preferably in the order of 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, and 0.09 or more. When it is desired to further improve weather resistance, the above ratio is further preferably set to 0.10 or more, and is further preferably in the order of 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, or 0.25 or more.
[0301] On the other hand, if the above ratio is increased excessively, the transmittance characteristics of the glass will decrease, and the tendency of the stability of the glass to decrease will also become stronger. Therefore, the above ratio is preferably below 0.36, and more preferably below 0.35, below 0.34, below 0.33, below 0.32, below 0.31, below 0.30, below 0.29, and below 0.28.
[0302] The ZnO content may be 0%, 0% or more, or more than 0%. ZnO is a component that can be appropriately added for reasons such as adjusting the thermal stability of the glass, but there is a tendency to reduce the weather resistance of the glass. In addition, from the viewpoint of fully ensuring the introduction amount of P2O5 as an essential component, the upper limit of its content is preferably 20.0% or less, and 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, and 5.0% or less are more preferred in this order. In the case of giving priority to the introduction effect of other components, the ZnO content may also be 4.0% or less, 3.0% or less, 2.0% or less, or 1.0% or less. On the other hand, when ZnO is introduced to adjust the thermal stability of the glass or lower Tg and / or Tm, the amount is preferably in the order of 0.4% or more, 0.6% or more, 0.8% or more, 1.0% or more, 1.2% or more, 1.4% or more, 1.6% or more, 1.8% or more, and 2.0% or more.
[0303] The glass is preferably basically composed of the above components, but may contain other components within a range that does not hinder the effects of the above components. In addition, the glass may contain inevitable impurities.
[0304] For example, in order to adjust the weather resistance, mechanical strength, or improve the thermal stability of the glass, Nb2O5 and ZrO2 may be appropriately introduced in an amount exceeding 0%, 0.1%, or 0.2% as components other than the above components, but their contents are preferably 5.0% or less, and more preferably in the order of 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, and 0.3% or less. The contents of these components may be 0% respectively.
[0305] In order to adjust the weather resistance and mechanical strength of the glass or improve the thermal stability without affecting the transmittance of the glass, more than 0%, 0.1% or 0.2% of TiO2, WO3, and Bi2O3 may be appropriately introduced as components other than the above components, and their contents are preferably 4.0% or less, and more preferably in the order of 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, and 0.3% or less. The contents of these components may also be 0%.
[0306] Pb, As, Cd, Tl, Be, and Se are all toxic. Therefore, the glass preferably does not contain these elements as glass components.
[0307] U, Th, and Ra are all radioactive elements. Therefore, the glass preferably does not contain these elements as glass components.
[0308] V, Cr, Mn, Fe, Co, Ni, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Tm can increase the coloring of the glass and become a source of fluorescence. Therefore, in the above-mentioned glass, the total content of these elements based on the oxides is preferably set to 10 mass ppm or less, and it is more preferable not to contain these elements as glass components.
[0309] Among them, V2O5 is preferably not used due to its toxicity. That is, in one embodiment, glasses 1 to 6 are preferably glasses that do not contain V ions, and in the glass composition based on oxides (molar basis), the V2O5 content is preferably 1.0% or less, more preferably 0.3% or less, 0.1% or less, and 0.01% or less, and more preferably no V2O5.
[0310] As an example, as the ratio of V2O5 to the essential component Li2O, the ratio of V2O5 content to Li2O content (V2O5 / Li2O) is preferably 0.0080 or less, and more preferably 0.0048 or less, 0.0028 or less, 0.0018 or less, and 0.0014 or less in this order.
[0311] CoO reduces the transmittance of the glass in the visible region and is toxic, so it is preferably not used. That is, in one embodiment, glasses 1 to 6 are preferably glasses that do not contain Co ions, and preferably do not contain CoO in the glass composition based on oxides.
[0312] The raw materials for introducing Ge and Ta into glass are expensive, so it is preferred that the glass does not contain these elements as glass components.
[0313] Sb (Sb2O3), Sn (SnO2), Ce (CeO2) and SO3 are elements that can be added optionally and function as clarifiers. Among them, Sb (Sb2O3) is a clarifier with a significant clarification effect.
[0314] Sn (SnO2) and Ce (CeO2) have a smaller clarification effect than Sb (Sb2O3). If these clarifiers are added in large amounts, there is a tendency to cause the coloring of the glass to become stronger. Therefore, when adding clarifiers, it is preferred to add Sb (Sb2O3) while considering the effect of coloring caused by the addition.
[0315] The contents of the components that can function as clarifiers described below are values in the glass composition based on oxides.
[0316] The Sb2O3 content is expressed as a percentage. That is, when the total content of all glass components other than Sb2O3, SnO2, CeO2 and SO3 in terms of oxide is set to 100.0 mass%, the Sb2O3 content is preferably less than 2.0 mass%, and is more preferably in the order of 1.5 mass% or less, 1.2 mass% or less, 1.0 mass% or less, 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, 0.2 mass% or less, and less than 0.1 mass%. The Sb2O3 content may also be 0 mass%. However, from the perspective of promoting the oxidation of glass and improving the transmittance in the visible region, the Sb2O3 content can be set to 0.01 mass% or more, or it can be set to 0.02 mass% or more, 0.03 mass% or more, 0.04 mass% or more, 0.05 mass% or more, 0.06 mass% or more, or 0.08 mass% or more.
[0317] The SnO2 content is also expressed as an additional ratio. That is, when the total content of all glass components other than SnO2, Sb2O3, CeO2 and SO3 in terms of oxide is set to 100.0 mass%, the SnO2 content is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, 0.9 mass% or less, and more preferably in the order of 0.8 mass%, 0.7 mass%, 0.6 mass%, 0.5 mass%, 0.4 mass%, 0.3 mass%, 0.2 mass%, and 0.1 mass%. The SnO2 content may also be 0 mass%. By making the SnO2 content within the above range, the clarity of the glass can be improved.
[0318] The CeO2 content is also expressed as an additional ratio. That is, when the total content of all glass components other than CeO2, Sb2O3, SnO2 and SO3 in terms of oxide is set to 100.0 mass%, the CeO2 content is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, less than 0.9 mass%, and more preferably in the order of less than 0.8 mass%, less than 0.7 mass%, less than 0.6 mass%, less than 0.5 mass%, less than 0.4 mass%, less than 0.3 mass%, less than 0.2 mass%, and less than 0.1 mass%. The CeO2 content may also be 0 mass%. By making the CeO2 content within the above range, the clarity of the glass can be improved.
[0319] The SO3 content is also expressed as an additional ratio. That is, when the total content of all glass components other than SO3, Sb2O3, SnO2, and CeO2 in terms of oxides is set to 100.0 mass%, the SO3 content is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, further preferably less than 0.5 mass%, and further preferably less than 0.1 mass%. The SO3 content may also be 0 mass%. By setting the SO3 content to the above range, the clarity of the glass can be improved.
[0320] <Glass Properties>
[0321] (Transmittance characteristics)
[0322] The above-mentioned glass is suitable as glass for near infrared cut filter. In the present invention and this specification, "transmittance" means external transmittance including reflection loss unless otherwise specified.
[0323] Regarding the near infrared blocking ability, the wavelength at which the transmittance reaches 50% at a wavelength of 550nm or more, i.e. the half value λ T 50 can be used as an indicator, the transmittance T1200 at a wavelength of 1200nm can be used as an indicator, the average value of the transmittance in the range of wavelengths 1100nm to 800nm (recorded as "Ave. T1100-800") can be used as an indicator, and the transmittance T750 at a wavelength of 750nm can be used as an indicator.
[0324] The glass can also show high transmittance in the visible region. Regarding the transmittance in the visible region, the transmittance T400 at a wavelength of 400 nm can be used as an indicator, and the transmittance T600 at a wavelength of 600 nm can be used as an indicator.
[0325] The transmittance characteristics of glass are values obtained by the following method.
[0326] The glass sample is processed into parallel and optically polished planes, and the external transmittance at a wavelength of 200 to 1200 nm is measured. The external transmittance also includes the reflection loss of light on the test surface.
[0327] The intensity of light incident vertically on one plane after optical polishing is defined as intensity A, and the intensity of light emitted from the other plane is defined as intensity B. The spectral transmittance B / A including reflection loss is calculated. The wavelength at which the spectral transmittance reaches 50% at a wavelength of 550nm or more is defined as the half-value λ. T50. The spectral transmittance at a wavelength of 400 nm is set to T400, the spectral transmittance at a wavelength of 600 nm is set to T600, and the spectral transmittance at a wavelength of 1200 nm is set to T1200. The average value of the spectral transmittance in the range of wavelengths from 1100 nm to 800 nm is set to Ave.T1100-800, and the spectral transmittance at a wavelength of 750 nm is set to T750.
[0328] In addition, when the glass to be measured is not glass of the converted thickness, the thickness of the glass can be set to d, the transmittance at each wavelength λ can be converted by the following formula A, and various conversion values can be calculated based on the converted transmittance characteristics.
[0329] Formula A: T(λ) = (1 - R(λ)) 2 ×exp(log e ((T0(λ) / 100) / (1-R(λ)) 2 )×d / d0)×100
[0330] In formula A, T(λ): converted transmittance at wavelength λ (%), T0(λ): measured transmittance at wavelength λ (%), d: converted thickness (mm), d0: glass thickness (mm), R(λ) = ((n(λ) - 1) / (n(λ) + 1)) 2 : The reflectivity at wavelength λ, n(λ): refractive index at wavelength λ. Here, calculations were performed assuming that n(λ)=1.51680 and R(λ)=0.042165 are constants.
[0331] A high value of T600, which is the transmittance in the red region, and a low value of T1200, which is the transmittance in the near-infrared region, can mean that both the transmittance in the visible region and the near-infrared blocking ability are improved. In addition, a high value of T400, which is the transmittance in the purple region, can also mean that the transmittance in the visible region is improved.
[0332] From the above viewpoints, the preferred ranges of T400, T600 and T1200 are as follows.
[0333] Regarding T400, it is preferably 70% or more, and more preferably in the order of 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, and 80% or more. T400 may be, for example, 98% or less, 97% or less, or 96% or less, but a higher T400 may mean better visible light transmittance, and therefore, it is also preferably higher than the values exemplified above.
[0334] Regarding T600, it is preferably 50% or more, and more preferably 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, and 75% or more. T600 may be, for example, 90% or less, 85% or less, or 80% or less, but a higher T600 may also mean better visible light transmittance, and therefore, it is also preferably higher than the values exemplified above.
[0335] Regarding T1200, it is preferably 30% or less, and more preferably 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, and 1% or less. For the purpose of taking visible light transmittance into consideration, T1200 may be, for example, 1% or more, 3% or more, 5% or more, or 7% or more, but a lower T1200 may mean a better near-infrared shielding ability, and therefore, it is also preferably lower than the values exemplified above.
[0336] In one embodiment, T1200 may be β1% or less.
[0337] β1 is calculated by the following formula B1, where R is the O / P ratio.
[0338] (Formula B1)
[0339] β1=64×R-170
[0340] In one embodiment, T1200 may be equal to or less than the numerical values represented by β2, β3, β4, β5, and β6 represented by the following formulas B2 to B6 (unit: %), where R represents the O / P ratio.
[0341] Formula B2: β2 = 64 × R-175
[0342] Formula B3: β3=64×R-180
[0343] Formula B4: β4 = 80 × R - 220
[0344] Formula B5: β5 = 80 × R-224
[0345] Formula B6: β6 = 80 × R - 228
[0346] The wavelength at which the spectral transmittance reaches 50% at a wavelength of 550nm or above, i.e., the half-value λ T 50 is preferably 600 nm or more, and more preferably 610 nm or more, 613 nm or more, 615 nm or more, 617 nm or more, 620 nm or more, 623 nm or more, 625 nm or more, and 628 nm or more in this order. T 50 is preferably 650nm or less, and more preferably 647nm or less, 645nm or less, 643nm or less, 641nm or less, 640nm or less, 639nm or less, and 638nm or less. From the viewpoint of achieving both thinning of the glass and improvement of the near-infrared shielding ability, it is preferred that the wavelength at which the spectral transmittance reaches 50% at a wavelength of 550nm or more, i.e., the half value λ T 50. The glass thickness given below is preferably 0.25 mm or less.
[0347] In addition, since the above-mentioned glass has excellent absorption characteristics in the near-infrared region, "Ave.T1100-800" can be suppressed to 15% or less. "Ave.T1100-800" is preferably 14% or less, and more preferably 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.3% or less, 1.0% or less, 0.3% or less, 0.1% or less, 0.03% or less, and 0.01% or less in this order.
[0348] In addition, since the glass has excellent absorption characteristics in the near-infrared region, T750 can be suppressed to 25% or less. T750 is preferably 24% or less, and more preferably in the order of 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.3% or less, 1.0% or less, 0.3% or less, 0.1% or less, 0.03% or less, and 0.01% or less.
[0349] As described in detail later, the glass can be used as glass for a near-infrared cut filter having a thickness of 0.25 mm or less in one embodiment.
[0350] Regarding the above-mentioned glass, as the preferred transmittance characteristics for the glass for near-infrared cutoff filter thinned to a thickness of 0.25 mm or less, the following (a) to (h) can be cited. The above-mentioned glass preferably satisfies one or more of the following (a) to (h), and may also satisfy two or more. By adjusting the glass composition as described above, a glass having a preferred transmittance characteristic can be obtained.
[0351] (a) The wavelength λ at which the external transmittance including reflection loss reaches 50% at a wavelength of 550 nm or more T The thickness of the glass reaching 50 to 633 nm is 0.25 mm or less. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.
[0352] Regarding (a) above, the wavelength λ at which the external transmittance including reflection loss reaches 50% at a wavelength of 550 nm or more is T The thickness of the glass having a wavelength of 50 to 633 nm is 0.25 mm or less, and more preferably is within the thickness range described later for the thickness of the near infrared cut filter. This also applies to the following (b), (e) and (f).
[0353] (b) The thickness of the glass having an external transmittance of 50% including reflection loss at a wavelength of 550 nm or more and a wavelength of 633 nm is 0.25 mm or less. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less. β1 is a value calculated by the following formula B1. In formula B1, R is the O / P ratio of the above glass.
[0354] (Formula B1)
[0355] β1=64×R-170
[0356] As described above, T1200 may be β2% or less, β3% or less, β4% or less, β5% or less, or β6% or less.
[0357] (c) As the transmittance characteristic converted to a thickness of 0.11 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% T 50 In the range of 600nm to 650nm, the external transmittance T1200 including reflection loss at a wavelength of 1200nm is 30% or less, and the external transmittance T400 including reflection loss at a wavelength of 400nm is 70% or more.
[0358] (d) As the transmittance characteristic converted to a thickness of 0.21 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% T 50 In the range of 600nm to 650nm, the external transmittance T1200 including reflection loss at a wavelength of 1200nm is 25% or less, and the external transmittance T400 including reflection loss at a wavelength of 400nm is 70% or more.
[0359] (e) The thickness of the glass at a wavelength of 645 nm, at which the external transmittance including reflection loss at a wavelength of 550 nm or more reaches 50%, is 0.25 mm or less. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.
[0360] (f) The wavelength λ at which the external transmittance including reflection loss reaches 50% at a wavelength of 550 nm or more T The thickness of the glass reaching 50 to 645nm is less than 0.25mm. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600nm is more than 50%, and the external transmittance T1200 including reflection loss at a wavelength of 1200nm is less than β1%, where β1 is the value calculated by the formula B1 recorded above.
[0361] (g) As the transmittance characteristic converted to a thickness of 0.23 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% T 50 In the range of 600nm to 650nm, the external transmittance T1200 including reflection loss at a wavelength of 1200nm is 18% or less, and the external transmittance T400 including reflection loss at a wavelength of 400nm is 70% or more.
[0362] (h) As the transmittance characteristic converted to a thickness of 0.25 mm, the wavelength λ at which the external transmittance including reflection loss reaches 50% T 50 In the range of 600nm to 650nm, the external transmittance T1200 including reflection loss at a wavelength of 1200nm is less than 16%, and the external transmittance T400 including reflection loss at a wavelength of 400nm is more than 70%.
[0363] (Weather resistance)
[0364] The glass can show excellent weather resistance by having the composition described above. Regarding weather resistance, for example, the evaluation result of weather resistance evaluated by visual observation by the method described in the embodiments described later can be used as an indicator, and the evaluation result is preferably any result from S to D, more preferably any result from S to C, further preferably any result from S to B, further preferably S or A, and further preferably S.
[0365] In addition, the haze value measured by a haze meter may be used as an index for weather resistance. Glass having a haze value of 15% or less is cited as an example of glass having better weather resistance.
[0366] With regard to weather resistance, it is more preferred that the evaluation result by visual observation described above is S or A (preferably S), and the haze value measured by a haze meter is 15% or less.
[0367] (Glass transition temperature Tg, temperature Tm at which the endothermic reaction due to melting converges)
[0368] The glass transition temperature of the glass is not particularly limited. From the viewpoint of improving the transmittance of the glass in the short wavelength range by improving the meltability of the glass and reducing the burden on the annealing furnace and the molding device, Tg is preferably 450°C or less, and more preferably in the order of 440°C or less, 430°C or less, 420°C or less, 410°C or less, and 400°C or less. From the viewpoint of improving the chemical durability and / or heat resistance of the glass, Tg is preferably 250°C or more, and more preferably in the order of 260°C or more, 270°C or more, 280°C or more, 290°C or more, and 300°C or more.
[0369] The Tg value of glass can be controlled by adjusting the contents of Li2O, Na2O, and K2O, their total content, the content of ZnO, the content of MgO, the content of Al2O3, and their total content, etc.
[0370] The temperature Tm at which the endothermic reaction based on melting of the above-mentioned glass converges is not particularly limited. The lower the Tm, the better the solubility. There is a tendency that devitrification does not occur in the glass even if molding is performed at a higher viscosity. In addition, there is a tendency that the better the solubility, the more the transmittance of the glass in the visible region of the short wavelength range can be improved. From these viewpoints, Tm is preferably below 890°C, and further preferably in the order of below 880°C, below 870°C, below 860°C, below 850°C, below 840°C, below 830°C, below 820°C, below 810°C, below 800°C, below 790°C, below 780°C, below 770°C, below 760°C, below 750°C, below 740°C, below 730°C, below 720°C, below 710°C, below 700°C, below 690°C, below 680°C, below 670°C, below 660°C, and below 650°C. The lower limit of Tm is not particularly limited. However, if Tm is too low, the weather resistance of the glass tends to decrease. Therefore, Tm may be 500°C or higher, 550°C or higher, 580°C or higher, 600°C or higher, 620°C or higher, or 640°C or higher.
[0371] The Tm value of glass can be controlled by adjusting the contents of Li2O, Na2O, and K2O, their total content, the content of ZnO, the content of MgO, the content of Al2O3, and their total content, etc.
[0372] (proportion)
[0373] Since it is related to the lightness of the element or device provided with the filter, it is preferable that the near infrared cut filter is light. In view of this point, the specific gravity of the above-mentioned glass is preferably 3.40 or less, and more preferably in the order of 3.35 or less, 3.30 or less, 3.25 or less, 3.20 or less, 3.15 or less, 3.10 or less, 3.05 or less, 3.00 or less, 2.95 or less, 2.90 or less, 2.85 or less, 2.80 or less, 2.75 or less, 2.70 or less, 2.65 or less, and 2.60 or less.
[0374] The specific gravity may be, for example, 2.0 or more or 2.4 or more. From the above viewpoint, the specific gravity is preferably lower, and therefore, it is also preferably lower than the values exemplified here.
[0375] (Molar volume)
[0376] There is no particular limitation on the molar volume M / D of the glass. From the perspective of increasing the near-infrared absorption capacity by increasing the amount of CuO per unit volume, it is preferred that the molar volume of the glass be smaller. If P2O5, La2O3, Y2O3, Gd2O3, BaO, K2O, etc. are replaced with Li2O, the molar volume can be reduced. If Al2O3, CuO, Na2O are replaced with Li2O, the molar volume can be slightly reduced. On the other hand, even if CaO, ZnO, and SrO are replaced with Li2O, the molar volume will not change significantly. If MgO is replaced with Li2O, there is a tendency for the molar volume to increase. These tendencies can be taken into account to adjust the molar volume of the glass by adjusting the glass composition. The molar volume is preferably 45cc / mol or less, and more preferably 43cc / mol or less, 42cc / mol or less, 41cc / mol or less, 40cc / mol or less, 39.5cc / mol or less, 39.0cc / mol or less, 38.5cc / mol or less, 38.0cc / mol or less, and 37.5cc / mol or less.
[0377] On the other hand, from the perspective of maintaining the weather resistance of the glass, the molar volume can also be increased. From this point of view, the molar volume of the above-mentioned glass can be greater than 34.0cc / mole, or greater than 35.0cc / mole, greater than 36.0cc / mole, greater than 36.5cc / mole, greater than 37.0cc / mole, greater than 37.5cc / mole, greater than 38.0cc / mole, greater than 38.5cc / mole, greater than 39.0cc / mole, or greater than 39.5cc / mole.
[0378] <Glass Manufacturing Method>
[0379] The above-mentioned glass can be obtained by mixing, melting and molding various glass raw materials. Regarding the production method, reference can also be made to the description described below.
[0380] The near-infrared absorbing glass is suitable as glass for near-infrared cut-off filters. In addition, the near-infrared absorbing glass can also be applied to optical elements (lenses, etc.) other than near-infrared cut-off filters, and can also be applied to various glass products and can be variously deformed.
[0381] [Near infrared cut filter]
[0382] One embodiment of the present invention relates to a near infrared cut filter (hereinafter, also simply referred to as a “filter”) made of the above-mentioned near infrared absorbing glass.
[0383] The glass constituting the above-mentioned optical filter is as described above.
[0384] A specific example of the method for producing the optical filter will be described below, but the following method is for illustrative purposes only and does not limit the present invention.
[0385] For molten glass, glass raw materials such as phosphates, oxides, carbonates, nitrates, sulfates, and fluorides are appropriately used, and the raw materials are weighed and mixed in a manner to achieve the desired composition, and then melted in a melting container such as a platinum crucible, for example, at 800°C to 1100°C. At this time, in order to suppress the volatilization of volatile components, a lid of platinum or the like can also be used. In addition, the melting can be carried out in the atmosphere, and in order to suppress the change in the valence of Cu, an oxygen atmosphere can also be formed, or oxygen bubbling can be carried out in the molten glass. The glass in the molten state becomes a homogenized molten glass with fewer bubbles (preferably without bubbles) by stirring and clarifying. It should be noted that after clarifying the glass at 900°C to 1100°C, in order to promote the oxidation of the glass, the glass can also be obtained after the glass is cooled to 800°C to 1000°C. However, it is not expected that the melting temperature and the clarifying temperature are lower than the liquidus temperature of the glass for a long time.
[0386] After stirring and clarifying the molten glass, the glass is made to flow out, and after slowly cooling, it is formed into a desired shape. When making the glass flow out, if it is cooled to a temperature near the liquidus temperature and the viscosity of the glass is increased, convection of the flowing glass is less likely to occur, and wave lines are less likely to occur, so it is preferred. As the slow cooling rate, a rate between -50°C / hr and -1°C / hr can be selected, and -30°C / hr and -10°C / hr can also be selected.
[0387] As a glass forming method, known methods such as casting, pipe outflow, rolling, pressing, etc. can be used. The formed glass is transferred to an annealing furnace preheated to near the glass transition temperature and slowly cooled to room temperature. In this way, a near infrared cutoff filter can be manufactured.
[0388] An example of a molding method is described below. A mold consisting of a flat and horizontal bottom surface, a pair of side walls sandwiching the bottom surface and facing each other in parallel, and a weir plate located between the pair of side walls and closing one side opening is prepared. Homogenized molten glass is injected into the mold at a constant outflow rate from a platinum alloy pipe. The injected molten glass is spread out in the mold and molded into a glass plate that is limited to a certain width by a pair of side walls. The molded glass plate is continuously pulled out from the opening of the mold. Here, by appropriately setting the molding conditions such as the shape, size, and outflow rate of the molten glass of the mold, it is possible to mold a large and thick glass block. The molded glass mold is transferred to an annealing furnace preheated to near the glass transition temperature and slowly cooled to room temperature. The glass molded body after the strain is removed by slow cooling is subjected to mechanical processing such as slicing, grinding, and polishing. In this way, a near-infrared cutoff filter in a shape corresponding to the purpose, such as a plate shape or a lens shape, can be obtained. Alternatively, a method may be adopted in which a preform made of the above glass is formed, heated, softened, and then press-formed (particularly, a precision press-forming method in which the final product is press-formed without subjecting the optical functional surface to mechanical processing such as grinding and polishing). An optical multilayer film may also be formed on the surface of the optical filter as required.
[0389] The near infrared cut filter can have both excellent near infrared blocking capability and high transmittance in the visible region. With such a near infrared cut filter, the color sensitivity correction of the semiconductor imaging element can be performed well.
[0390] In addition, the near infrared cut filter can be applied to a camera device by combining it with a semiconductor image sensor. The semiconductor image sensor has a semiconductor imaging element such as a CCD or CMOS installed in the component, and the light receiving part is covered by a light-transmitting member. The light-transmitting member can be used as a near infrared cut filter at the same time, or the light-transmitting member and the near infrared cut filter can be different members.
[0391] The imaging device may include an optical element such as a lens or a prism on the light receiving surface of the semiconductor image sensor for forming an image of the object to be imaged.
[0392] Furthermore, by using the above-mentioned near infrared cut filter, it is possible to provide an imaging device that can perform color sensitivity correction well and obtain an image with excellent image quality.
[0393] The above-mentioned near-infrared cut-off filter can be a near-infrared cut-off filter with a thickness of less than 0.25mm in one embodiment. In recent years, due to the emergence of smart phones, the tendency to reduce the thickness of the camera of the imaging element is significant, and with this, the near-infrared cut-off filter is also expected to exert performance with a thinner thickness. As such a near-infrared cut-off filter, the above-mentioned near-infrared cut-off filter is also preferred. The thickness of the above-mentioned near-infrared cut-off filter can be less than 0.24mm, less than 0.23mm, less than 0.22mm, less than 0.21mm, less than 0.20mm, less than 0.19mm, less than 0.18mm, less than 0.17mm, less than 0.16mm, less than 0.15mm, less than 0.14mm, less than 0.13mm or less than 0.12mm. The thickness of the above-mentioned near-infrared cut-off filter can be, for example, 0.21mm or 0.11mm. In addition, the thickness of the near infrared cut filter can be, for example, 0.50 mm or more, but is not limited thereto. In the present invention and this specification, "thickness" refers to the thickness of the sample in the area where the transmittance is measured, and can be measured by a thickness gauge, a micrometer, etc. For example, the thickness of the approximate center of the position where the transmitted light passes can be measured, or the thickness of multiple points can be measured within the light spot of the transmitted light and the average value can be taken.
[0394] Regarding the transmittance characteristics of the near-infrared cut filter, the above description regarding glasses 1 to 6 can be referred to. Furthermore, regarding the physical properties of the near-infrared cut filter, the above description regarding glasses 1 to 6 can also be referred to.
[0395] Example
[0396] Hereinafter, the present invention will be described in more detail with reference to the examples, but the present invention is not limited to the examples.
[0397] [Examples 1 to 66, Comparative Examples X, A to D]
[0398] As glass raw materials, phosphates, fluorides, carbonates, nitrates, oxides, etc. are weighed and mixed in such a way that 150 g to 300 g of glass of the composition shown in Table 1 can be obtained, and then placed in a platinum crucible or a quartz crucible, melted at 800°C to 1000°C for 80 minutes to 100 minutes, stirred to degas and homogenize, and then poured into a preheated mold and formed into a given shape. The obtained glass molded body is transferred to an annealing furnace heated to near the glass transition temperature and slowly cooled to room temperature. A test piece is cut out from the obtained glass, and after mirror polishing on both sides to a thickness of about 0.2 mm, various evaluations are performed by the following methods.
[0399] [Evaluation method]
[0400] <Transmittance characteristics>
[0401] The transmittance of each test piece at a wavelength of 200 to 1200 nm was measured using a spectrophotometer. Based on the measurement results, the transmittance was converted into values of half-value 645 nm, half-value 633 nm, thickness 0.11 mm, thickness 0.21 mm, thickness 0.23 mm, and thickness 0.25 mm, and the half-value (unit: nm), T400, T600, T1200, Ave. T1100-800 (unit: %) were obtained.
[0402] <Glass transition temperature Tg, temperature Tm at which the endothermic reaction due to melting converges>
[0403] The glass transition temperature Tg and the temperature Tm at which the endothermic reaction due to melting converged were measured using a differential scanning calorimeter (DSC8270) manufactured by Rigaku Corporation at a heating rate of 10°C / min. The measurement temperature range was set to a range of room temperature to 1050°C.
[0404] <Specific Gravity>
[0405] The specific gravity was measured by the Archimedean method.
[0406] <Molar volume>
[0407] The molar volume was calculated from the measured specific gravity using the method described above.
[0408] <Evaluation classification of weather resistance>
[0409] Each test piece was kept in a constant temperature and humidity chamber at a temperature of 85° C. and a relative humidity of 85% for 3.5 hours, and then visually evaluated for appearance under a fluorescent lamp. Based on the evaluation results, weather resistance was evaluated according to the following criteria.
[0410] S: Fogging and / or precipitates observed on the surface are extremely slight.
[0411] A: Fogging and / or precipitates observed on the surface are slight.
[0412] B: Slightly strong fogging and / or generation of precipitates were observed on the surface.
[0413] C: Wetting of the surface showing deliquescence was observed but was slight, and / or thick precipitates were generated.
[0414] D: Deliquescence to such an extent that the plate thickness is significantly reduced and / or generation of precipitates covering the plain glass are not observed.
[0415] E: Deliquescence to such an extent that the plate thickness is significantly reduced is observed, and / or precipitates are generated to such an extent that plain glass is not observed.
[0416]
[0417]
[0418]
[0419]
[0420]
[0421]
[0422]
[0423]
[0424]
[0425]
[0426]
[0427]
[0428]
[0429]
[0430]
[0431]
[0432]
[0433]
[0434]
[0435]
[0436]
[0437] From the results shown in the above table, it can be confirmed that the glasses of Examples 1 to 66 have high transmittance in the visible region (purple region to red region) even when thinned, are excellent in near-infrared shielding ability, and suppress deterioration in weather resistance.
[0438] Regarding weather resistance, based on the comparison between Examples 1 to 58 and Example 59, it was confirmed that the weather resistance of Examples 1 to 58, which had a larger value of "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)", was better than that of Example 59, in which the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" was 0.
[0439] Regarding the comparison between Example 59 and Example 60, the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is 0, and the value of "(Na2O+K2O+ZnO) / Li2O" exceeds 1.4. Example 60, which is larger than Example 59, has a greater degree of deliquesce than Example 59 and is slightly inferior in weather resistance.
[0440] In Comparative Example X, the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" exceeds 0, but the value of "(Na2O+K2O+ZnO) / Li2O" is large, exceeding 11, and the weather resistance is low.
[0441] Comparative Example A, Comparative Example B, and Comparative Example C are glasses made of only three components, namely, P2O5, Li2O, and CuO, and have very low weather resistance.
[0442] In Comparative Example D, the O / P ratio exceeded 3.2, and the desired transmittance characteristics were not obtained.
[0443] In the examples described above in which the evaluation based on visual observation for weather resistance was classified as S or A, haze values were also obtained for Examples 25, 33, 56, and 61 to 66 using a haze meter. The obtained haze values are shown in Table 8.
[0444] [Table 8]
[0445]
[0446] As shown in Table 8, compared with Example 25 and Example 33 which were rated A in the evaluation category of weather resistance evaluation based on visual observation, Examples 56 and 61 to 66 which were rated S in the evaluation category of weather resistance evaluation based on visual observation had lower haze values of 15% or less.
[0447] Based on the above results, it can be confirmed that in order to further reduce the haze value to below 15% while taking into account both the improvement of transmittance in the visible region and the improvement of near-infrared blocking ability, the preferred O / P ratio is in the range of 3.00 to 3.15 and the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" (unit: mol %) is in the range of 10.0% to 40.0%.
[0448] Finally, summarize the above methods.
[0449] According to one embodiment, glasses 1 to 6 described in detail above are provided.
[0450] In one embodiment, in glasses 1 to 6, the Al 2 O 3 content may be less than 2.0 mol %.
[0451] In one embodiment, in glasses 1 to 6, the total content of Al 2 O 3 , La 2 O 3 , Y 2 O 3 , and Gd 2 O 3 (Al 2 O 3 + La 2 O 3 + Y 2 O 3 + Gd 2 O 3 ) may be 0.1 mol % or more.
[0452] In one embodiment, glasses 1 to 6 may have the following transmittance characteristics.
[0453] Half value λ T 50 The thickness of the glass reaching 633nm is 0.25mm or less, and the above half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm.
[0454] At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.
[0455] Half value λ T 50 The thickness of the glass reaching 633nm is 0.25mm or less, and the above half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm.
[0456] At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less.
[0457] β1 is a value calculated by the following formula B1,
[0458] (Formula B1)
[0459] β1=64×R-170
[0460] In the above formula B1, R is the above ratio (O ion / P ion).
[0461] As the transmittance characteristic converted to a thickness of 0.11 mm, the half value λ T 50In the range of 600nm~650nm, the above half value λT 50 is the wavelength at which the external transmittance including reflection loss reaches 50%, the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less, and the external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more.
[0462] As the transmittance characteristic converted to a thickness of 0.21 mm, the half value λ T 50In the range of 600nm~650nm, the above half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50%, the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 25% or less, and the external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more.
[0463] Half value λ T 50 The thickness of the glass reaching 645nm is less than 0.25mm, and the above half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at a wavelength of 550nm or more. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600nm is more than 50%, and the external transmittance T1200 including reflection loss at a wavelength of 1200nm is less than 30%.
[0464] Half value λ T 50 The thickness of the glass reaching 645nm is less than 0.25mm, and the above half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at a wavelength of 550nm or more. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200nm is β1% or less.
[0465] The above β1 is a value calculated by the following formula B1,
[0466] (Formula B1)
[0467] β1=64×R-170
[0468] In the above formula B1, R is the above ratio (O ion / P ion).
[0469] According to one embodiment, there is provided a near infrared cut filter made of the near infrared absorbing glass.
[0470] It should be understood that the embodiments disclosed this time are all exemplary and not restrictive. The scope of the present invention is defined by the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0471] For example, by adjusting the composition of the glass composition exemplified above as described in the specification, the near infrared absorbing glass according to one embodiment of the present invention can be obtained.
[0472] Furthermore, it is of course possible to arbitrarily combine two or more of the features described as examples or as preferred ranges in the specification.
Claims
1. A near infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions and Y ions, Contains P ions, Li ions and Cu ions as essential cations, contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, The total content of B2O3 and SiO2 (B2O3+SiO2) is less than 3.0%, CuO content is α1% or more, α1 is a value calculated by the following formula 1, Formula 1: α1=70400×exp(-2.855×R) In the formula 1, R is the ratio (O ions / P ions), As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
2. A near infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions and Y ions, Contains P ions, Li ions and Cu ions as essential cations, and contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, The total content of B2O3 and SiO2 (B2O3+SiO2) is less than 3.0%, The near-infrared absorbing glass satisfies the following formula 2: Formula 2: C-3200×exp(-2.278×R)≥0 In the formula 2, C is the average CuO content per molar volume of glass (unit: mmol / cc), R is the ratio (O ions / P ions), As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
3. A near infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions, Contains P ions, Li ions and Cu ions as essential cations, and contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, A1 calculated by the following formula 3 is 2500 or more, Formula 3: A1={O(P)-O(others)}×Cu In the formula 3, O(P) represents the amount of oxygen in the oxide that constitutes P ions in the oxide-based glass composition. O(others) represents the amount of oxygen obtained by removing O(P) from the amount of oxygen in the oxide constituting the main cation in the oxide-based glass composition. Cu represents the CuO content on a molar basis in the glass composition on an oxide basis, As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
4. A near-infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions, Contains P ions, Li ions and Cu ions as essential cations, and contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, A2 calculated by the following formula 4 is 700 or more, Formula 4: A2={O(P)-O(others)}×C In the formula 4, C is the average CuO content per molar volume of glass (unit: mmol / cc), O(P) represents the amount of oxygen in the oxide that constitutes P ions in the oxide-based glass composition. O(others) represents the amount of oxygen obtained by removing O(P) from the amount of oxygen in the oxide constituting the main cation in the oxide-based glass composition. As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
5. A near infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions and Y ions, Contains P ions, Li ions and Cu ions as essential cations, and contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, CuO content is α2% or more, α2 is a value calculated by the following formula 5, Formula 5: α2=76522×exp(-2.855×R) In the formula 5, R is the ratio (O ions / P ions), As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
6. A near-infrared absorbing glass comprising four or more main cations, wherein the main cations are selected from P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions and Y ions, Contains P ions, Li ions and Cu ions as essential cations, and contains at least O ions as anions, The ratio of the content of O ions to the content of P ions (O ions / P ions) is 3.10 or less, In the glass composition expressed as anion %, the content of O ions is 90.0 anion % or more. In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO+Al2O3) is less than 8.0%, V2O5 content is less than 1.0%, The ratio of the total of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, The near-infrared absorbing glass satisfies the following formula 6, Formula 6: C-3478×exp(-2.278×R)≥0 In Formula 6, C is the average CuO content per molar volume of glass (unit: mmol / cc), R is the ratio (O ions / P ions), As transmittance characteristics converted to a thickness of 0.21 mm, an external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more, and an external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 10% or less.
7. The near infrared absorbing glass according to any one of claims 1 to 6, wherein The total content of Na2O content and K2O content is less than 15.0 mol%.
8. The near infrared absorbing glass according to any one of claims 1 to 7, wherein The Al2O3 content is less than 2.0 mol%.
9. The near infrared absorbing glass according to any one of claims 1 to 8, wherein The total content of Al2O3, La2O3, Y2O3 and Gd2O3 (Al2O3+La2O3+Y2O3+Gd2O3) is 0.1 mol% or more.
10. The near infrared absorbing glass according to any one of claims 1 to 9, wherein Half value λ T 50 The thickness of the glass reaching 633nm is less than 0.25mm, and the half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.
11. The near infrared absorbing glass according to any one of claims 1 to 9, wherein Half value λ T 50 The thickness of the glass reaching 633nm is less than 0.25mm, and the half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm. At the thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less, β1 is a value calculated by the following formula B1, Formula B1: β1=64×R-170 In the formula B1, R is the ratio (O ions / P ions).
12. The near infrared absorbing glass according to any one of claims 1 to 9, wherein As the transmittance characteristic converted to a thickness of 0.11 mm, the half value λ T 50 In the range of 600nm to 650nm, the external transmittance T1200 including reflection loss at a wavelength of 1200nm is less than 30%, and the external transmittance T400 including reflection loss at a wavelength of 400nm is more than 70%, and the half value λ T 50 is the wavelength at which external transmittance including reflection losses reaches 50%.
13. The near infrared absorbing glass according to any one of claims 1 to 9, wherein As the transmittance characteristic converted to a thickness of 0.21 mm, the half value λ T 50 is in the range of 600nm to 650nm, the half value λ T 50 is the wavelength at which external transmittance including reflection losses reaches 50%.
14. The near infrared absorbing glass according to any one of claims 1 to 9, wherein Half value λ T 50 The thickness of the glass reaching 645nm is less than 0.25mm, and the half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm. At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.
15. The near infrared absorbing glass according to any one of claims 1 to 9, wherein Half value λ T 50 The thickness of the glass reaching 645nm is less than 0.25mm, and the half value λ T 50 is the wavelength at which the external transmittance including reflection loss reaches 50% at wavelengths above 550nm. At the thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less, The β1 is a value calculated by the following formula B1: Formula B1: β1=64×R-170 In the formula B1, R is the ratio (O ions / P ions). 16 . A near infrared cut filter, comprising the near infrared absorbing glass according to claim 1 .
Citation Information
Patent Citations
Colored glass
JP2014012630A
Edge-coating glass for laser disks
US4229220A